Anti-glare anti-reflection component, polarizing plate, surface plate and image display device having the anti-glare anti-reflection component, and screening method for anti-glare anti-reflection component

By forming an anti-glare layer and a low refractive index layer on the substrate and controlling the average value of the film thickness difference Δd of the low refractive index layer, the coloring and highlight problems of the existing anti-glare anti-reflective films in the oblique direction are solved, and a better visual effect is achieved.

CN115516342BActive Publication Date: 2025-03-14DAI NIPPON PRINTING CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180033222.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-09
Filing Date
2021-03-09
Publication Date
2025-03-14
Estimated Expiration
2041-03-09

AI Technical Summary

Technical Problem

The existing anti-glare anti-reflective film is prone to coloring and local highlights when viewed from the oblique direction.

Method used

An anti-glare anti-reflective member with an anti-glare layer and a low refractive index layer is formed on the substrate, and the average value of the film thickness difference Δd of the low refractive index layer is controlled to be 7.0 nm or more and 40.0 nm or less.

Benefits of technology

It effectively suppresses the coloring when observing from the oblique direction and reduces the situation where bright spots are observed locally.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115516342B_ABST
    Figure CN115516342B_ABST
Patent Text Reader

Abstract

The present invention provides an anti-glare anti-reflection component that can suppress coloring when observed from an oblique direction, thereby suppressing the situation where a bright spot is locally observed. An anti-glare anti-reflection component that has an anti-glare layer and a low refractive index layer on a substrate, wherein when the film thickness difference of the low refractive index layer in an arbitrary 2 mm×2 mm area of ​​the anti-glare anti-reflection component is defined as Δd, the average of Δd is greater than or equal to 7.0 nm and less than or equal to 40.0 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an anti-glare anti-reflection member, a polarizing plate, a surface plate, and an image display device including the anti-glare anti-reflection member, and a method for selecting the anti-glare anti-reflection member. Background Art

[0002] In display devices such as liquid crystal display devices, organic EL display devices, micro LED display devices, mini LED display devices, display devices using quantum dots, and display cabinets, it is known to provide an anti-reflection component on the surface of the display device in order to improve visibility.

[0003] In recent years, in addition to televisions, in-vehicle displays such as car navigation systems, digital signage displays, tablet computers, smartphones, and other touch panel image display devices that are operated by users directly touching the screen have become popular, and anti-reflection components are also provided in these devices.

[0004] Examples of such antireflection members include those in which a hard coat layer and an antireflection layer are sequentially formed on a substrate (for example, Patent Documents 1 and 2).

[0005] The antireflection members of Patent Documents 1 and 2 can suppress reflection of external light, but have a problem of being reflected in the background due to their smooth surfaces.

[0006] Therefore, an antiglare antireflection film has been proposed in which an antiglare layer and an antireflection layer are sequentially formed on a substrate (for example, Patent Document 3).

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2016-218179

[0010] Patent Document 2: Japanese Patent Application Publication No. 2020-8877

[0011] Patent Document 3: Japanese Patent Application Publication No. 2018-197829 Summary of the invention

[0012] Problems to be solved by the invention

[0013] The antiglare antireflection film of Patent Document 3 can reduce the background reflection compared with Patent Documents 1 and 2. However, the antiglare antireflection film of Patent Document 3 has the problem that it is often colored and observed when observed from an oblique direction, or a bright spot is observed locally.

[0014] In view of the above-mentioned problems, the present disclosure aims to provide an anti-glare, anti-reflection component that can suppress coloring when observed from an oblique direction and thereby suppress the situation where bright spots are locally observed, a polarizing plate, a surface plate and an image display device having the anti-glare, anti-reflection component, and a method for screening the anti-glare, anti-reflection component.

[0015] Means for solving problems

[0016] In order to solve the above-mentioned problems, the present disclosure provides the following solutions [1] to [5].

[0017] [1] An antiglare antireflection member comprising an antiglare layer and a low refractive index layer on a substrate, wherein:

[0018] When the difference in film thickness of the low refractive index layer in an arbitrary 2 mm×2 mm region of the antiglare antireflection member is defined as Δd, the average of Δd is 7.0 nm or more and 40.0 nm or less.

[0019] [2] A polarizing plate comprising: a polarizer; a first transparent protective plate disposed on one side of the polarizer; and a second transparent protective plate disposed on the other side of the polarizer, wherein at least one of the first transparent protective plate and the second transparent protective plate is the anti-glare anti-reflection component described in [1], and the polarizing plate is configured in such a manner that the anti-glare anti-reflection component is disposed with the surface on the low refractive index layer side facing the side opposite to the polarizer.

[0020] [3] A surface plate for an image display device, which is formed by laminating an anti-glare anti-reflection component to a resin plate or a glass plate, wherein the anti-glare anti-reflection component is the anti-glare anti-reflection component described in [1], and the surface plate for the image display device is configured in a manner such that the surface on the low refractive index layer side faces the side opposite to the resin plate or the glass plate.

[0021] [4] An image display device, wherein the anti-glare, anti-reflection component described in [1] is arranged on the display element in a manner such that the surface on the low refractive index layer side faces the side opposite to the display element, and the anti-glare, anti-reflection component is arranged on the surface.

[0022] [5] A method for screening anti-glare and anti-reflection components, comprising the steps (1) and (2) below:

[0023] (1) The thickness difference Δd of the low refractive index layer in an arbitrary 2 mm×2 mm region of an antiglare antireflection member having an antiglare layer and a low refractive index layer on a substrate was measured, and the average of Δd was calculated.

[0024] (2) The average Δd is 7.0 nm or more and 40.0 nm or less as a determination condition, and members satisfying the determination condition are selected as antiglare antireflection members.

[0025] Effects of the Invention

[0026] The anti-glare anti-reflection component disclosed herein, and the polarizing plate, the surface plate, and the image display device having the anti-glare anti-reflection component can suppress coloration when observed from an oblique direction, thereby suppressing the situation where a bright spot is locally observed. In addition, the screening method of the anti-glare anti-reflection component disclosed herein can stably screen out the anti-glare anti-reflection component that can suppress coloration when observed from an oblique direction, thereby suppressing the situation where a bright spot is locally observed. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a cross-sectional view schematically illustrating one embodiment of the anti-glare anti-reflection member of the present disclosure.

[0028] Figure 2 This is a diagram for explaining the process of generating a difference in film thickness of the low refractive index layer.

[0029] Figure 3 This is a diagram for explaining the measurement position of the height profile when calculating Δd.

[0030] Figure 4 This is a schematic cross-sectional view of a device for measuring the erosion rate of a substrate.

[0031] Figure 5 This is a schematic diagram showing a state in which a substrate is abraded by a test liquid containing pure water and spherical silica ejected from an ejection unit. DETAILED DESCRIPTION

[0032] Hereinafter, the antiglare antireflection member of the present disclosure will be described in detail.

[0033] In addition, the expression of the numerical range "AA to BB" in this specification means "AA or more and BB or less".

[0034] [Anti-glare and anti-reflective materials]

[0035] The anti-glare anti-reflection component disclosed herein is an anti-glare anti-reflection component having an anti-glare layer and a low refractive index layer on a substrate, and when the film thickness difference of the low refractive index layer in an arbitrary 2 mm×2 mm area of ​​the anti-glare anti-reflection component is defined as Δd, the average of Δd is greater than or equal to 7.0 nm and less than or equal to 40.0 nm.

[0036] Figure 1 This is a cross-sectional view schematically illustrating one embodiment of the anti-glare anti-reflection member of the present disclosure. Figure 1The anti-glare anti-reflection member 1000 has an anti-glare layer 200 and a low refractive index layer 300 in this order on a substrate 100. The anti-glare layer 200 has a binder resin 210 and particles 220.

[0037] exist Figure 1 In the anti-glare anti-reflection component, the film thickness of the low refractive index layer 300 is uneven. Specifically, the film thickness of the low refractive index layer on the convex portion of the anti-glare layer 200 is thinner, while the film thickness of the low refractive index layer on the flat portion of the anti-glare layer 200 is thicker. That is, Figure 1 The low refractive index layer has a predetermined film thickness difference Δd.

[0038] The thickness difference Δd of the low refractive index layer is considered to be Figure 2 Produced in the processes (a) to (c).

[0039] First, if Figure 2 As shown in (a), when the coating liquid for the low refractive index layer is applied to the anti-glare layer 200, the wet film thickness of the low refractive index layer on the convex portion of the anti-glare layer 200 is uniform with the wet film thickness of the low refractive index layer on the flat portion of the anti-glare layer 200. In this state, Δd is approximately 0. The wet film thickness refers to the film thickness in a state containing a solvent as a component other than the solid component.

[0040] Then, if Figure 2 As shown in (b), in the coating liquid for the low refractive index layer applied on the anti-glare layer 200, a part of the coating liquid for the low refractive index layer existing on the convex portion of the anti-glare layer 200 flows down to the flat portion side of the anti-glare layer 200 before and during the drying. As a result, the wet film thickness of the low refractive index layer on the convex portion of the anti-glare layer 200 becomes thinner than the wet film thickness of the low refractive index layer on the flat portion of the anti-glare layer 200.

[0041] Next, from Figure 2 The low refractive index layer coating liquid is dried in the state (b), and the binder resin is cured as needed to form a low refractive index layer. Figure 2 (c) state. Figure 2 In (c), the dry film thickness of the low refractive index layer on the convex portion of the anti-glare layer 200 becomes thinner than the dry film thickness of the low refractive index layer on the flat portion of the anti-glare layer 200. Thus, a film thickness difference Δd of the low refractive index layer is formed.

[0042] In this specification, the difference in thickness Δd of the low refractive index layer refers to the difference in thickness of the low refractive index layer when the anti-glare anti-reflection component is completed. For example, as described above, when the low refractive index layer is formed by a wet method, the difference in thickness of the low refractive index layer in the state where the coating liquid for the low refractive index layer is dried and then cured as needed, i.e., the anti-glare anti-reflection component is completed, is Δd.

[0043] The thickness difference Δd of the low refractive index layer can be adjusted by the surface shape of the anti-glare layer and the leveling property of the low refractive index layer, etc. A plurality of means can be listed to make the average Δd fall within the scope of the present disclosure. These means will be described later.

[0044] <Base material>

[0045] The substrate serves as a support for the antiglare layer and the low refractive index layer.

[0046] The substrate preferably has high light transmittance. Specifically, the substrate preferably has a total light transmittance of 90% or more in accordance with JIS K7361-1:1997.

[0047] Furthermore, the substrate preferably has a low haze. Specifically, the haze of the substrate in accordance with JIS K7136:2000 is preferably 3.0% or less, more preferably 2.0% or less.

[0048] Regarding the substrate, plastic and glass can be cited. From the perspective of being lightweight and easy to manufacture, the substrate is preferably made of plastic. Hereinafter, the plastic substrate is sometimes referred to as a plastic film. The glass plate as the substrate includes the so-called "Ultra-Thin Glass". Ultra-thin glass is sold by, for example, Samsung and Nippon Electric Glass.

[0049] The plastic film can be formed by one or more resins selected from the following resins: polyolefin resins such as polyethylene and polypropylene; vinyl resins such as polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl acetate copolymer, and ethylene-vinyl alcohol copolymer; polyester resins such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate; acrylic resins such as polymethyl (meth)acrylate and polyethyl (meth)acrylate; styrene resins such as polystyrene; polyamide resins such as nylon 6 or nylon 66; cellulose resins such as triacetyl cellulose; polycarbonate resins; polyimide resins; polyamide-imide resins; and various resins such as cyclic olefin resins obtained from cyclic olefins such as aromatic polyamide resins, norbornene, and dicyclopentadiene.

[0050] In order to improve the mechanical strength, the plastic film is preferably a stretched plastic film, more preferably a biaxially stretched plastic film.

[0051] Among plastic films, polyester films are preferred, and among them, biaxially stretched polyester films having excellent mechanical strength are preferred, and among them, biaxially stretched polyethylene terephthalate films are more preferred.

[0052] In order to suppress optical anisotropy, the in-plane retardation of a plastic film such as a biaxially stretched polyester film is preferably 1600 nm or less, more preferably 1400 nm or less, more preferably 1200 nm or less, and more preferably 1000 nm or less.

[0053] The in-plane phase difference is a value expressed by the following formula (1) based on the refractive index nx in the slow axis direction where the refractive index of the plastic film is the highest, the refractive index ny in the fast axis direction orthogonal to the slow axis direction, and the thickness T [nm] of the plastic film.

[0054] In-plane retardation (Re) = (nx-ny) × T [nm] (1)

[0055] The in-plane phase difference of 1600 nm or less means that the difference between nx and ny is small. By reducing the difference between nx and ny, the difference in reflectivity between the slow axis direction and the fast axis direction of the plastic film can be reduced, so it is easier to suppress the appearance from being deteriorated depending on the direction of observation. Regarding the appearance, bright spots and whitening can be listed.

[0056] In addition, for plastic films such as biaxially stretched polyester films, in order to reduce the in-plane phase difference, nx-ny is preferably 0.040 or less, more preferably 0.035 or less, and further preferably 0.030 or less. As a method for making nx to ny of the biaxially stretched polyester film within the above range, for example, a method of stretching at approximately the same ratio in the longitudinal and transverse directions can be cited.

[0057] In order to suppress warping, the thickness of the plastic film is preferably 5 μm or more, more preferably 20 μm or more, and further preferably 30 μm or more. In order to achieve thin film, the thickness of the plastic film is preferably 300 μm or less, more preferably 200 μm or less, further preferably 150 μm or less, and further preferably 90 μm or less.

[0058] It should be noted that the plastic film may be in the form of a plate having a thickness exceeding 500 μm. In addition, when flexibility is required for foldable applications, the thickness of the plastic film is preferably 10 μm or more and 40 μm or less. In addition, when glass is used in a component to which an anti-glare anti-reflection component is mounted, the thickness of the plastic film is preferably 40 μm or more and 100 μm or less in order to prevent the glass from scattering.

[0059] In order to achieve good strength, the thickness of the glass substrate is preferably 5 μm or more, more preferably 10 μm or more, and further preferably 30 μm or more. In addition, in order to achieve thin film, the thickness of the glass substrate is preferably 300 μm or less, more preferably 200 μm or less, further preferably 150 μm or less, and further preferably 90 μm or less. In the case where flexibility is required for foldable applications, the thickness of the glass substrate is preferably 10 μm or more and 40 μm or less, and more preferably 20 μm or more and 40 μm or less.

[0060] The tensile modulus of the substrate is preferably 3.5 GPa or more, more preferably 4.0 GPa or more, in order to improve the mechanical strength. The upper limit of the tensile modulus of the substrate is not particularly limited, but is preferably 5.5 GPa or less, more preferably 4.5 GPa or less.

[0061] In this specification, the tensile modulus of the substrate refers to the tensile modulus of JIS K 7127: 1999. The tensile modulus was measured on a sample having a length of 150 mm and a width of 10 mm. The tensile speed was 50 mm / min, and the distance between chucks was 100 mm.

[0062] Preferred ranges of the tensile modulus of the substrate include 3.5 GPa to 5.5 GPa, 3.5 GPa to 4.5 GPa, 4.0 GPa to 5.5 GPa, and 4.0 GPa to 4.5 GPa.

[0063] In order to suppress deformation of components in the image display device, the water vapor permeability of the substrate is preferably 200 g / m 2 / day or less, more preferably 100g / m 2 The lower limit of the water vapor permeability of the substrate is not particularly limited, but is preferably 5 g / m 2 / day or more, more preferably 10g / m 2 / day or more.

[0064] In this specification, water vapor permeability refers to the water vapor permeability based on JIS K7129-2: 2019. The temperature and relative humidity conditions for measuring the water vapor permeability are 40°C and 90%. In addition, before measuring the water vapor permeability, the sample for measurement is exposed to an atmosphere with a temperature of 23°C ± 5°C and a relative humidity of 40% or more and 65% or less for 30 minutes or more.

[0065] The water vapor transmission rate can be measured, for example, using a water vapor transmission rate measuring device manufactured by MOCON (trade name: PERMA TRAN).

[0066] The preferred range of the water vapor permeability of the substrate is 5 g / m 2 / day or more and 200g / m 2 / day or less, 5g / m 2 / day or more and 100g / m 2 / day or less, 10g / m 2 / day or more and 200g / m 2 / day or less, 10g / m 2 / day or more and 100g / m 2 / day or less.

[0067] <Erosion rate>

[0068] Regarding the plastic film as the substrate, the average of the erosion rates from the surface of the plastic film to a depth of 20 μm is defined as E. 0-20 When E 0-20 It is preferably 1.4 μm / g or more.

[0069] In this manual, E 0-20 It is measured under the following measurement conditions.

[0070] <Measurement conditions>

[0071] A test liquid is placed in a container: the test liquid is a mixture of pure water, a dispersion liquid, and spherical silica with an average particle size of 4.2 μm and within ±8% in a mass ratio of 968:2:30. The test liquid in the container is delivered to a nozzle. Compressed air is delivered to the nozzle to accelerate the test liquid in the nozzle, and a predetermined amount of the test liquid is vertically sprayed from the spray hole at the end of the nozzle to the plastic film so that the spherical silica in the test liquid collides with the plastic film. The cross-sectional shape of the nozzle is a square of 1 mm×1 mm, and the distance between the spray hole and the plastic film is 4 mm. In addition, the flow rate of the test liquid and the compressed air supplied to the nozzle, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are predetermined values ​​adjusted by the calibration described later.

[0072] After a predetermined amount of the test liquid is sprayed, the spraying of the test liquid is temporarily stopped.

[0073] After the injection of the test liquid was temporarily stopped, the cross-sectional profile of the portion of the plastic film that collided with the spherical silica in the test liquid was measured.

[0074] The following operation is performed until the depth of the cross-sectional profile exceeds 20 μm: the operation includes three steps, namely, the step of ejecting a specified amount of the test liquid from the ejection port, the step of temporarily stopping the ejection of the test liquid after ejecting the specified amount of the test liquid, and the step of measuring the cross-sectional profile after temporarily stopping the ejection of the test liquid. Then, in each cycle until the depth of the cross-sectional profile reaches 20 μm, the erosion rate (μm / g) of the plastic film is calculated by dividing the depth (μm) of the cross-sectional profile advanced in each cycle by the ejection amount (g) of the test liquid in each cycle. The erosion rate of the plastic film in each cycle until the depth of the cross-sectional profile reaches 20 μm is averaged to calculate the E 0-20 .

[0075] <Correction>

[0076] The test liquid is stored in the container. The test liquid in the container is delivered to the nozzle. Compressed air is delivered to the nozzle to accelerate the test liquid in the nozzle, and any amount of the test liquid is vertically sprayed from the spray hole at the end of the nozzle to the acrylic plate with a thickness of 2 mm, so that the spherical silica in the test liquid collides with the acrylic plate. The cross-sectional shape of the nozzle is a 1 mm × 1 mm square, and the distance between the spray hole and the acrylic plate is 4 mm.

[0077] After spraying an arbitrary amount of the test liquid, the spraying of the test liquid is temporarily stopped. After the spraying of the test liquid is temporarily stopped, the cross-sectional profile of the portion of the acrylic plate that collides with the spherical silica in the test liquid is measured.

[0078] The erosion rate (μm / g) of the acrylic plate was calculated by dividing the depth (μm) of the cross-sectional profile by the arbitrary amount (g).

[0079] The erosion rate of the acrylic plate is set as a qualified condition within the range of ±5% based on 1.88 (μm / g). The flow rates of the test liquid and the compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are adjusted to perform correction so that the erosion rate of the acrylic plate falls within the range.

[0080] Below, citing Figure 4 The measurement conditions of the erosion rate and the technical significance of the erosion rate calculated under the measurement conditions are explained. Figure 4 As such an apparatus for measuring the erosion rate, for example, there can be mentioned an MSE test apparatus (product number: "MSE-A203") manufactured by Palmeso Co., Ltd., and the like.

[0081] Under the erosion rate measurement conditions disclosed herein, first, a test liquid is placed in a container (11): the test liquid is a mixture of pure water, a dispersant, and spherical silica having an average particle size within ±8% of 4.2 μm in a mass ratio of 968:2:30. The test liquid is preferably stirred in the container (11).

[0082] As pure water, general-purpose pure water can be used. The resistivity value of pure water is usually 0.1 MΩ·cm or more and 15 MΩ·cm or less.

[0083] There is no particular limitation on the dispersant as long as it can disperse the spherical silica. Examples of the dispersant include a dispersant with a trade name of "Demol N" manufactured by Wako Pure Chemical Industries, Ltd.

[0084] The “average particle size is within ±8% based on 4.2 μm” means, in other words, that the average particle size is 3.864 μm or more and 4.536 μm or less.

[0085] In the measurement conditions of the erosion rate in the present specification, the “average particle size of spherical silica” is an average particle size measured as a volume average value d50 in particle size distribution measurement based on a laser diffraction method, and refers to a so-called “median particle size”.

[0086] Regarding the spherical silica, it is preferred that, in the result of the particle size distribution measurement, when the frequency of the particle size displayed as the maximum frequency is standardized to 100, the width of the particle size displayed as 50 is within ±10% based on 4.2μm. Regarding the "width of the particle size displayed as 50", when "the particle size displayed as 50 and the particle size in the positive direction of the particle size displayed as 100" is defined as X, and "the particle size displayed as 50 and the particle size in the negative direction of the particle size displayed as 100" is defined as Y, "the width of the particle size displayed as 50" is represented by "X~Y (μm)". It should be noted that in this specification, the "width of the particle size displayed as 50" is sometimes referred to as the "full width at half maximum of the particle size distribution".

[0087] As spherical silica having an average particle size within ±8% of 4.2 μm, there can be cited the model “MSE-BS-5-3” designated by Palmeso Co., Ltd. As spherical silica conforming to the model “MSE-BS-5-3” designated by Palmeso Co., Ltd., there can be cited, for example, the product number “BS5-3” of Potters-Ballotini Co., Ltd.

[0088] The test liquid in the container is sent to the nozzle 51. The test liquid can be sent to the nozzle through the test liquid pipe 21, for example. A flow meter 31 for measuring the flow rate of the test liquid is preferably arranged between the container 11 and the nozzle 51. The flow rate of the test liquid is set to the value adjusted by the calibration.

[0089] It should be noted that in Figure 4 In the embodiment, the nozzle 51 is arranged in a housing 52 constituting the injection unit 50 .

[0090] Compressed air is fed into the nozzle 51. The compressed air is fed into the nozzle through, for example, the compressed air pipe 22. In the nozzle, the compressed air is fed into a position preferably upstream of the position into which the test liquid is fed. The upstream side refers to the side away from the injection hole of the nozzle.

[0091] Preferably, a flow meter 32 for measuring the flow rate of the compressed air and a pressure gauge 42 for measuring the pressure of the compressed air are arranged before the compressed air reaches the nozzle 51. The compressed air can be supplied by an air compressor (not shown) or the like.

[0092] The flow rate and pressure of the compressed air are values ​​adjusted by the above-mentioned calibration.

[0093] When compressed air is supplied to the nozzle 51, the test liquid is accelerated while mixing with the compressed air. Then, the accelerated test liquid is ejected from the ejection hole at the end of the nozzle 51 and collides vertically with the plastic film 70. The plastic film is mainly abraded by the spherical silica particles in the test liquid.

[0094] It should be noted that a pressure gauge 41 for measuring the pressure of the test liquid in the nozzle is preferably disposed in the nozzle 51. The pressure gauge 41 is preferably located downstream of the position where the compressed air is fed and the position where the test liquid is fed.

[0095] The pressure of the test liquid in the nozzle 51 is a value adjusted by the above-mentioned calibration.

[0096] The test liquid sprayed from the spray hole at the end of the nozzle 51 is mixed with air and sprayed in a mist form. Therefore, the collision pressure of the spherical silica particles on the plastic film can be reduced. Therefore, the amount of wear of the plastic film caused by one spherical silica particle can be suppressed to a trace amount. Figure 5 FIG. 2 is a schematic diagram showing a state in which the plastic film 70 is worn by the test liquid containing pure water A1 and spherical silica A2 ejected from the ejection unit 50. Figure 5 In the figure, reference numeral A3 represents air, and reference numeral A4 represents the worn plastic film.

[0097] In addition, since the test liquid contains water with excellent cooling effect, the deformation and deterioration of the plastic film caused by the heat during collision can be substantially eliminated. In other words, abnormal wear of the plastic film can be substantially eliminated. In addition, water also has the effect of cleaning the surface of the worn plastic film to achieve stable wear. In addition, water has the effect of accelerating the spherical silica particles or controlling the flow of the test liquid.

[0098] In addition, since a large number of spherical silica particles collide with the plastic film, the influence of subtle differences in physical properties of individual spherical silica particles can be eliminated.

[0099] Furthermore, in the measurement conditions disclosed herein, the flow rate of the test liquid supplied to the nozzle, the flow rate of the compressed air supplied to the nozzle, the pressure of the compressed air supplied to the nozzle, and the pressure of the test liquid in the nozzle are set to the values ​​adjusted by the calibration, and the cross-sectional shape of the nozzle is determined to be a 1 mm × 1 mm square, and the distance between the injection hole and the plastic film is determined to be 4 mm, thereby determining the factors affecting the wear amount of the plastic film. It should be noted that the distance is Figure 4 The distance shown by "d" refers to the vertical distance between the spray hole as the end of the nozzle and the plastic film.

[0100] As is clear from the above description, the measurement conditions of the present disclosure can be said to be measurement conditions that can form statistically stable wear marks on the plastic film.

[0101] The plastic film 70 may be mounted on the sample mounting table 81 of the measuring device 500. Preferably, a laminated body is prepared by bonding the plastic film to a support body 82 such as a stainless steel plate, and the laminated body is mounted on the sample mounting table 81.

[0102] Preferably, the test liquid sprayed onto the plastic film 70 is recovered by the receiver 12 and returned to the container 11 through the return pipe 23 .

[0103] The measurement conditions of the present disclosure require that: after a predetermined amount of the test liquid is sprayed, the spraying of the test liquid is temporarily stopped; and after the spraying of the test liquid is temporarily stopped, the cross-sectional profile of the portion of the plastic film that collides with the spherical silica in the test liquid is measured.

[0104] The cross-sectional profile refers to the cross-sectional shape of the plastic film worn by the test fluid. The plastic film is mainly worn by the spherical silica particles in the test fluid.

[0105] The cross-sectional profile can be measured by, for example, a stylus-type surface shape measuring device or a laser interferometer-type surface shape measuring device, etc., a cross-sectional profile acquiring unit 60. It should be noted that the cross-sectional profile acquiring unit 60 is usually arranged at a position separated from the plastic film 70 when the test liquid is sprayed. Therefore, it is preferred that at least one of the plastic film 70 and the cross-sectional profile acquiring unit 60 is movable.

[0106] The cross-sectional profile measuring device of the MSE test device produced by Palmeso Co., Ltd., product number "MSE-A203", is a stylus type.

[0107] Furthermore, under the measurement conditions of the present disclosure, the following operation is performed until the depth of the cross-sectional profile exceeds 20 μm: the operation includes three steps, namely, a step of ejecting a specified amount of test liquid from an ejection port, a step of temporarily stopping the ejection of the test liquid after ejecting the specified amount of test liquid, and a step of measuring the cross-sectional profile after temporarily stopping the ejection of the test liquid, as one cycle.

[0108] By performing the above operation, the erosion rate of the plastic film in each cycle can be measured, and further, the variation in the erosion rate of the plastic film can be calculated.

[0109] The above cycle may be continued even after the depth of the cross-sectional profile exceeds 20 μm, but it is preferred to terminate the above cycle when the depth of the cross-sectional profile exceeds 20 μm. In addition, the reason for performing the measurement "from the surface of the plastic film to a depth of 20 μm" is that the physical properties of the plastic film tend to change near the surface, but tend to become more stable toward the inside.

[0110] In this specification, the erosion rate of each cycle can be expressed by the following [Formula 1].

[0111] Erosion rate of each cycle (μm / g) = Depth of cross-sectional profile advanced in each cycle (μm) / Injection amount of test fluid in each cycle (g) [Formula 1]

[0112] In Formula 1, "the depth (μm) of the cross-sectional profile advanced in each cycle" refers to the value represented by "yx" when the depth of the cross-sectional profile of the nth cycle is defined as x (μm) and the depth of the cross-sectional profile of the n+1th cycle is defined as y (μm). In addition, with respect to the first cycle, the depth (μm) of the cross-sectional profile of the first cycle is equivalent to the "depth (μm) of the cross-sectional profile advanced in each cycle".

[0113] It should be noted that, in this specification, the depth of the cross-sectional profile at the nth cycle refers to the depth at the deepest position of the cross-sectional profile at the nth cycle. n is an integer greater than or equal to 1.

[0114] In Formula 1, the "injection amount (g) of the test liquid in each cycle" is a "fixed amount" in principle, but may vary slightly in each cycle.

[0115] The injection amount of the test liquid in each cycle is not particularly limited, but the lower limit is preferably 0.5 g or more, more preferably 1.0 g or more, and the upper limit is preferably 3.0 g or less, more preferably 2.0 g or less.

[0116] Under the measurement conditions disclosed herein, the erosion rate (μm / g) was calculated in each cycle until the depth of the cross-sectional profile reached 20 μm. Then, the erosion rate in each cycle until the depth of the cross-sectional profile reached 20 μm was averaged to calculate E 0-20 .

[0117] The above cycle was performed until the depth of the cross-sectional profile exceeded 20 μm, but the data of the cycle in which the depth of the cross-sectional profile exceeded 20 μm was removed from the data used to calculate E 0-20 excluded from the data.

[0118] Generally speaking, a plastic film is easily damaged when it is soft, and is difficult to be damaged when it is hard. The present inventors have studied using the values ​​obtained by evaluation based on PICODENTOR and including the depth direction, such as Martens hardness, indentation hardness, and elastic recovery work, as indices of pencil hardness. However, the above parameters such as Martens hardness, indentation hardness, and elastic recovery work cannot be used as indices of pencil hardness.

[0119] In addition, the strength of plastic films tends to increase when stretched. Specifically, uniaxially stretched plastic films tend to have better pencil hardness than unstretched plastic films, and biaxially stretched plastic films tend to have better pencil hardness than uniaxially stretched plastic films. However, even biaxially stretched plastic films may have insufficient pencil hardness.

[0120] The inventors studied the erosion rate as an index of the pencil hardness of plastic films. As described above, a plastic film is easily damaged when it is soft and difficult to be damaged when it is hard, so it is believed that a plastic film with a small erosion rate can achieve good pencil hardness. However, the inventors found that by increasing the erosion rate E 0-20 The present inventors have found that the erosion rate of a biaxially stretched plastic film is greater than that of a uniaxially stretched plastic film, and that the quality of the pencil hardness of a biaxially stretched plastic film can be determined by the erosion rate.

[0121] The reason why the erosion rate of the plastic film and the pencil hardness are correlated is considered to be as follows.

[0122] As described above, under the measurement conditions of the present disclosure, the test liquid containing water and spherical silica is mixed with air and sprayed in a mist form. Therefore, the collision pressure generated by the spherical silica particles on the plastic film is suppressed to be low. Therefore, in the case where the plastic film is soft, it can be considered that the stress when the spherical silica collides with the plastic film is easily dispersed, so the plastic film is not easily worn and the erosion rate becomes low. On the other hand, in the case where the plastic film is harder, it can be considered that the stress when the spherical silica collides with the plastic film is difficult to disperse, so the plastic film is easily worn and the erosion rate increases.

[0123] In addition, it can be considered that the difference in the erosion rate in the biaxially stretched plastic film is caused by the difference in the degree of stretching of the molecular chain and the difference in the orientation of the molecules. For example, in principle, for a biaxially stretched plastic film, the molecules are stretched in the plane, but sometimes there are molecules that are not fully stretched locally in the plane. In this way, it can be considered that if the proportion of molecules that are not fully stretched locally in the plane increases, the biaxially stretched plastic film becomes soft locally and the erosion rate decreases. In addition, it can be considered that even biaxially stretched plastic films with the same in-plane phase difference show different erosion rates due to the difference in the local orientation of the molecules.

[0124] In order to make the pencil hardness good, the E 0-20 It is preferably 1.4 μm / g or more.

[0125] E 0-20 It is preferably 1.6 μm / g or more, more preferably 1.8 μm / g or more, further preferably 1.9 μm / g or more, and further preferably 2.0 μm / g or more.

[0126] In order to make the plastic film not easy to break, E 0-20 It is preferably 3.0 μm / g or less, more preferably 2.5 μm / g or less, and further preferably 2.2 μm / g or less.

[0127] E 0-20Embodiments of the preferred numerical range of can include, for example, 1.4 μm / g or more and 3.0 μm / g or less, 1.4 μm / g or more and 2.5 μm / g or less, 1.4 μm / g or more and 2.2 μm / g or less, 1.6 μm / g or more and 3.0 μm / g or less, 1.6 μm / g or more and 2.5 μm / g or less, 1.6 μm / g or more and 2.2 μm / g or less, 1.8 μm / g or more and 3.0 μm / g or less, 1 .8μm / g or more and 2.5μm / g or less, 1.8μm / g or more and 2.2μm / g or less, 1.9μm / g or more and 3.0μm / g or less, 1.9μm / g or more and 2.5μm / g or less, 1.9μm / g or more and 2.2μm / g or less, 2.0μm / g or more and 3.0μm / g or less, 2.0μm / g or more and 2.5μm / g or less, 2.0μm / g or more and 2.2μm / g or less.

[0128] In addition, by setting the erosion rate of the plastic film to the above-mentioned range, when stress is applied to the anti-glare anti-reflection component of the present invention, it is easy to relax the stress applied to the low refractive index layer. Therefore, by setting the erosion rate of the plastic film to the above-mentioned range, it is possible to easily suppress the rupture of the outer shell layer of the hollow particles in the low refractive index layer. With regard to the anti-glare anti-reflection component of the present invention, since there is a predetermined film thickness difference in the low refractive index layer, it is easy to achieve a relationship of "the density of hollow particles per unit area of ​​the low refractive index layer on the convex portion of the anti-glare layer < the density of hollow particles per unit area of ​​the low refractive index layer on the flat portion of the anti-glare layer". Therefore, from the perspective of suppressing the rupture of the outer shell of the hollow particles in the low refractive index layer on the flat portion of the anti-glare layer, it is preferred to set the erosion rate of the plastic film to the above-mentioned range.

[0129] As a case where stress is applied to the anti-glare anti-reflection component, the anti-glare anti-reflection component may be curved or bent. For example, when the anti-glare anti-reflection component is applied to a curved image display device or a foldable image display device, the anti-glare anti-reflection component may be curved or bent.

[0130] As described above, by setting the erosion rate of the plastic film within the above range, the shell layer of the hollow particles in the low refractive index layer is suppressed from breaking, thereby further suppressing coloration when observed from an oblique direction and making it easier to suppress local bright spots from being observed.

[0131] The calibration is performed before measuring the above-mentioned erosion rate.

[0132] For example, the correction can be performed as follows.

[0133] <Correction>

[0134] The test liquid is stored in the container. The test liquid in the container is delivered to the nozzle. Compressed air is delivered to the nozzle to accelerate the test liquid in the nozzle, and any amount of the test liquid is vertically sprayed from the spray hole at the end of the nozzle to the acrylic plate with a thickness of 2 mm, so that the spherical silica in the test liquid collides with the acrylic plate. The cross-sectional shape of the nozzle is a 1 mm × 1 mm square, and the distance between the spray hole and the acrylic plate is 4 mm.

[0135] After spraying an arbitrary amount of the test liquid, the spraying of the test liquid is temporarily stopped. After the spraying of the test liquid is temporarily stopped, the cross-sectional profile of the portion of the acrylic plate that collides with the spherical silica in the test liquid is measured.

[0136] The erosion rate (μm / g) of the acrylic plate was calculated by dividing the depth (μm) of the cross-sectional profile by the above-mentioned arbitrary amount (g).

[0137] The erosion rate of the acrylic plate is set as a qualified condition within the range of ±5% based on 1.88 (μm / g). The flow rates of the test liquid and the compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are adjusted to perform correction so that the erosion rate of the acrylic plate falls within the range.

[0138] The test fluid used in the calibration is the same as the test fluid used in the measurement conditions to be performed later.

[0139] In addition, the measuring device used for calibration is the same as the measuring device used under the measurement conditions to be performed later.

[0140] The difference between the calibration and the measurement conditions to be performed later lies in that, for example, an acrylic plate with a thickness of 2 mm as a standard sample is used as a sample in the calibration, whereas a plastic film is used as a sample in the measurement conditions.

[0141] The acrylic plate with a thickness of 2 mm as the standard sample is preferably a polymethyl methacrylate plate. In addition, for the acrylic plate with a thickness of 2 mm as the standard sample, when the average erosion rate of the acrylic plate measured under the following measurement condition A is defined as AcE, AcE is preferably 1.786 μm / g or more and 1.974 μm / g or less. In addition, as the spherical silica in the following measurement condition A, the spherical silica with the model "MSE-BS-5-3" specified by Palmeso Co., Ltd. can be cited. Examples of spherical silica that conforms to the model number “MSE-BS-5-3” designated by Palmeso Co., Ltd. include a product number “BS5-3” produced by Potters-Ballotini Co., Ltd.

[0142] <Measurement Condition A>

[0143] The following test liquid is stored in a container: the test liquid is a mixture of pure water, a dispersant, and spherical silica with an average particle size within ±8% based on 4.2 μm in a mass ratio of 968:2:30. The test liquid in the container is delivered to a nozzle. Compressed air is delivered to the nozzle to accelerate the test liquid in the nozzle, and a predetermined amount of the test liquid is sprayed vertically from the spray hole at the end of the nozzle relative to the acrylic plate, so that the spherical silica in the test liquid collides with the acrylic plate. The cross-sectional shape of the nozzle is a 1 mm × 1 mm square, and the distance between the spray hole and the acrylic plate is 4 mm. In addition, regarding the flow rates of the test liquid and the compressed air supplied to the nozzle, the pressure of the compressed air, and the pressure of the test liquid in the nozzle, the flow rate of the test liquid is greater than 100 ml / minute and less than 150 ml / minute, the flow rate of the compressed air is greater than 4.96 L / minute and less than 7.44 L / minute, the pressure of the compressed air is greater than 0.184 MPa and less than 0.277 MPa, and the pressure of the test liquid in the nozzle is greater than 0.169 MPa and less than 0.254 MPa.

[0144] After 4 g of the test liquid was sprayed, the spraying of the test liquid was temporarily stopped.

[0145] After the injection of the test liquid was temporarily stopped, the cross-sectional profile of the portion of the acrylic plate that collided with the spherical silica in the test liquid was measured.

[0146] Then, AcE, which is the erosion rate of the acrylic plate, was calculated by dividing the depth (μm) of the cross-sectional profile by 4 g, which is the injection amount of the test liquid. The unit of AcE is “μm / g”.

[0147] During the calibration, the erosion rate of the acrylic plate is set as a qualified condition within the range of ±5% based on 1.88 (μm / g), and the flow rates of the test liquid and the compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are adjusted so that the erosion rate of the acrylic plate is within the said range.

[0148] In addition, the phrase “the erosion rate is within ±5% based on 1.88 (μm / g)” means, in other words, that the erosion rate is 1.786 (μm / g) or more and 1.974 (μm / g) or less.

[0149] <σ 0-20 / E 0-20 >

[0150] Regarding the plastic film, it is preferable that the deviation of the erosion rate calculated from the erosion rate from the surface of the plastic film to a depth of 20 μm is defined as σ 0-20 When 0-20 / E 0-20 Less than 0.100.

[0151] In this specification, σ 0-20 The erosion rate can be calculated from the erosion rate in each cycle until the depth of the cross-sectional profile reaches 20 μm under the above-mentioned measurement conditions.

[0152] σ 0-20 / E 0-20 represents the coefficient of variation of the erosion rate, σ 0-20 / E 0-20 Small means that the erosion rate is unlikely to change in the thickness direction of the plastic film. 0-20 / E 0-20 When the value is 0.100 or less, the erosion rate in the thickness direction is stable and the pencil hardness can be easily improved.

[0153] In addition, when there is a region with local weak strength in the plastic film, when stress is applied to the anti-glare anti-reflection component, physical changes such as deformation are likely to occur starting from the region with weak strength. And, as a result, damage and cracks may occur in the low refractive index layer. 0-20 / E 0-20 It is preferable to set the value to 0.100 or less because defects that occur starting from a region with local weak strength can be easily suppressed.

[0154] σ 0-20 / E 0-20 The upper limit of is more preferably 0.080 or less, further preferably 0.070 or less, further preferably 0.060 or less, further preferably 0.055 or less.

[0155] σ 0-20 / E 0-20 The smaller the value of , the more uniform the film quality in the thickness direction of the plastic film. When the film quality in the thickness direction of the plastic film is uniform, there is a tendency for stress to propagate easily in the thickness direction. Therefore, σ 0-20 / E 0-20 It is preferably 0.020 or more, and more preferably 0.035 or more.

[0156] About σ 0-20 / E 0-20 Embodiments of the preferred numerical range include, for example, 0.020 to 0.100, 0.020 to 0.080, 0.020 to 0.070, 0.020 to 0.060, 0.020 to 0.055, 0.035 to 0.100, 0.035 to 0.080, 0.035 to 0.070, 0.035 to 0.060, and 0.035 to 0.055.

[0157] In order to make the erosion rate of the plastic film within the above range, it is preferable to uniformly stretch the molecules within the surface of the plastic film.

[0158] Plastic films can be produced, for example, by a commonly used sequential biaxial stretching method. In the stretching in the flow direction of the sequential biaxial stretching, if the stretching time is shortened, the erosion rate tends to decrease, and if the stretching time is prolonged, the erosion rate tends to increase. The reason for this is believed to be that if the stretching time is short, it is difficult for the molecules in the surface of the plastic film to be stretched evenly, while on the other hand, if the stretching time is long, it is easy for the molecules in the surface of the plastic film to be stretched evenly. That is, in order to make E 0-20 Furthermore, by appropriately increasing the stretching ratio to a level that does not cause deviation in physical properties while extending the stretching time, E can be more easily increased. 0-20 It is 1.4 μm / g or more.

[0159] For the substrate, for the purpose of improving the adhesion with the anti-glare layer, a general chemical treatment and a general physical treatment can be implemented. In addition, for the purpose of improving the adhesion, a primer layer can also be formed between the substrate and the anti-glare layer.

[0160] <Anti-glare layer>

[0161] The antiglare layer is a layer having a concavoconvex shape.

[0162] The anti-glare layer can be formed, for example, by (A) a method using an embossing roll or an embossing film, (B) etching treatment, (C) molding by a mold, (D) formation of a coating film by coating, etc. Among these methods, if emphasis is placed on obtaining a stable surface shape, (C) molding by a mold is preferred, and if emphasis is placed on productivity and multi-variety coping, (D) formation of a coating film by coating is preferred.

[0163] The antiglare layer may be formed of only a resin, but preferably contains a binder resin and particles.

[0164] 《Binder resin》

[0165] The binder resin preferably includes a cured product of a curable resin composition. Examples of the cured product of the curable resin composition include a cured product of a thermosetting resin composition and a cured product of an ionizing radiation curable resin composition. In order to obtain better mechanical strength, a cured product of an ionizing radiation curable resin composition is preferred.

[0166] The thermosetting resin composition is a composition containing at least a thermosetting resin and is a resin composition that is cured by heating.

[0167] Examples of the thermosetting resin include acrylic resin, polyurethane resin, phenolic resin, urea melamine resin, epoxy resin, unsaturated polyester resin, silicone resin, etc. For the thermosetting resin composition, a curing agent is added to these curable resins as needed.

[0168] The ionizing radiation curable resin composition is a composition containing a compound having an ionizing radiation curable functional group. In this specification, the "compound having an ionizing radiation curable functional group" is also referred to as an "ionizing radiation curable compound".

[0169] Ionizing radiation refers to electromagnetic waves or charged particle beams that have energy quanta that can cause molecules to polymerize or crosslink. Ultraviolet rays or electron beams are usually used. In addition, electromagnetic waves such as X-rays and gamma rays, and charged particle beams such as alpha rays and ion rays can also be used.

[0170] As the ionizing radiation curable functional group, there can be listed ethylenically unsaturated bond groups such as (meth) acryloyl, vinyl, and allyl, as well as epoxy, oxetanyl, etc. As the ionizing radiation curable compound, a compound having an ethylenically unsaturated bond group is preferred, and a compound having two or more ethylenically unsaturated bond groups is more preferred, among which a multifunctional (meth) acrylate compound having two or more ethylenically unsaturated bond groups is further preferred.

[0171] As the multifunctional (meth) acrylate compound, any one of a monomer and an oligomer can be used, but an oligomer is preferred. That is, the anti-glare layer preferably comprises a cured product of a multifunctional (meth) acrylate oligomer. The cured product of the multifunctional (meth) acrylate oligomer can make the surface hardness of the anti-glare anti-reflection component good, while being able to suppress the excessive curing shrinkage of the anti-glare layer, and suppressing the uneven elevation difference of the anti-glare layer from becoming too large. Therefore, by making the anti-glare layer include a cured product of a multifunctional (meth) acrylate oligomer, it is possible to easily make the average of Δd less than 40.0nm.

[0172] The ratio of the cured product of the multifunctional (meth)acrylate oligomer to the total binder resin in the antiglare layer is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and further preferably 100% by mass.

[0173] In addition, the anti-glare layer may contain a binder resin other than the cured product of the multifunctional (meth)acrylate oligomer within a range not impairing the effects of the present disclosure.

[0174] The weight average molecular weight of the multifunctional (meth)acrylate oligomer is preferably 500 or more and 5,000 or less, and more preferably 1,000 or more and 3,000 or less.

[0175] By making the weight average molecular weight of the oligomer be 500 or more, it is possible to suppress the formation of large concave-convex tilts due to excessive curing shrinkage of the anti-glare layer, and it is easy to make the average of Δd be less than 40.0nm. In addition, when the weight average molecular weight of the oligomer is too large, the leveling property of the anti-glare layer is reduced, and there is a tendency that the convex part of the anti-glare layer becomes steep. Therefore, by making the weight average molecular weight of the oligomer be 5000 or less, it is also possible to easily make the average of Δd be less than 40.0nm.

[0176] In this specification, the weight average molecular weight refers to a polystyrene-equivalent value measured by gel permeation chromatography.

[0177] Preferred ranges of the weight average molecular weight of the polyfunctional (meth)acrylate oligomer include 500 to 5,000, 500 to 3,000, 1,000 to 5,000, and 1,000 to 3,000.

[0178] Examples of the bifunctional (meth)acrylate monomer in the polyfunctional (meth)acrylate compound include ethylene glycol di(meth)acrylate, bisphenol A tetraethoxy diacrylate, bisphenol A tetrapropoxy diacrylate, and 1,6-hexanediol diacrylate.

[0179] Examples of the trifunctional or higher-functional (meth)acrylate monomer include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol tetra(meth)acrylate, and isocyanuric acid-modified tri(meth)acrylate.

[0180] The (meth)acrylate monomer may be one in which a part of the molecular skeleton is modified, and one modified with ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, alkyl, cyclic alkyl, aromatic, bisphenol, or the like may be used.

[0181] Examples of the polyfunctional (meth)acrylate oligomer include (meth)acrylate polymers such as urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, and polyether (meth)acrylate.

[0182] Urethane (meth)acrylate is obtained, for example, by reaction of a polyol and an organic diisocyanate with a hydroxy (meth)acrylate.

[0183] Furthermore, in order to adjust the viscosity of the anti-glare layer coating solution, etc., a monofunctional (meth)acrylate may be added as an ionizing radiation curable compound.

[0184] Examples of the monofunctional (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, and isobornyl (meth)acrylate.

[0185] For the above-mentioned ionizing radiation curable compound, one kind can be used alone or two or more kinds can be used in combination. In addition, in the anti-glare layer coating solution, in addition to the ionizing radiation curable compound, a polymer can also be added in order to adjust the viscosity. About polymer, for example, a polymer having a weight average molecular weight exceeding 5000 and being less than 200,000 can be listed.

[0186] When the ionizing radiation curable compound is an ultraviolet curable compound, the ionizing radiation curable composition preferably contains additives such as a photopolymerization initiator and a photopolymerization accelerator.

[0187] The photopolymerization initiator may be one selected from the group consisting of acetophenone, benzophenone, α-hydroxyalkylphenone, Michler's ketone, benzoin, benzyl dimethyl ketal, benzoyl benzoate, α-acyl oxime ester, anthraquinone, halogenated ketone, thioxanthone, etc. Among them, α-hydroxyalkylphenone which is less prone to yellowing is preferred.

[0188] The photopolymerization accelerator can reduce polymerization hindrance caused by air during curing to accelerate the curing rate, and examples thereof include at least one selected from isopentyl p-dimethylaminobenzoate, ethyl p-dimethylaminobenzoate, and the like.

[0189] Particles

[0190] The average particle size of the particles is preferably 0.5 μm or more and 5.0 μm or less, more preferably 1.0 μm or more and 4.0 μm or less, and further preferably 1.0 μm or more and 3.0 μm or less.

[0191] In this specification, when it is expressed as "particles", it refers to monomers of granular materials that can form uneven surfaces on the surface of the anti-glare layer, and aggregates of granular materials. In other words, in this specification, when it is expressed as "particles", it does not mean so-called primary particles with a particle size of 0.1 μm or less. Examples of "monomers of granular materials that can form uneven surfaces on the surface of the anti-glare layer" include organic particles. Examples of "aggregates of granular materials that can form uneven surfaces on the surface of the anti-glare layer" include "aggregates formed by agglomeration of inorganic particles" and "aggregates formed by agglomeration of inorganic particles around organic particles with organic particles as cores".

[0192] When the average particle size of the particles is 0.5 μm or more, the anti-glare property can be easily improved. In addition, particles having an average particle size of more than 0.1 μm and less than 0.5 μm may form aggregates that may cause excessive anti-glare property and haze.

[0193] If the average particle size of the particles is too large, the concavo-convex shape of the anti-glare layer tends to become steep, and the low refractive index layer formed in a wet state on the convex portion of the anti-glare layer tends to flow into the flat portion of the anti-glare layer, so there is a tendency for the average of Δd to become larger. Therefore, by making the average particle size of the particles less than 5.0 μm, it is easy to make the average of Δd less than 40.0 nm. In addition, if the average particle size of the particles is too large, the influence of the refractive index of the particles themselves becomes larger, and the haze caused by scattering is easily generated.

[0194] As inorganic particles forming agglomerates, silicon dioxide, aluminum oxide, zirconium oxide and titanium dioxide can be listed, and silicon dioxide is preferred. As silicon dioxide, fumed silica, solid silicon dioxide, etc. can be listed. The primary particle size of the inorganic particles forming agglomerates is preferably 1 nm or more and 100 nm or less, and more preferably 1 nm or more and 50 nm or less.

[0195] Preferred ranges of the average particle size of the particles include 0.5 μm to 5.0 μm, 0.5 μm to 4.0 μm, 0.5 μm to 3.0 μm, 1.0 μm to 5.0 μm, 1.0 μm to 4.0 μm, and 1.0 μm to 3.0 μm.

[0196] In relatively large image display devices of 50 inches or more, vivid colors and image quality are sometimes emphasized, and anti-glare properties are sometimes required to be low enough to blur the outline of an object. In the above case, the average particle size of the particles is preferably 1.0 μm or more and 4.0 μm or less.

[0197] The average particle size of the particles can be calculated, for example, by the following operations (A1) to (A3).

[0198] (A1) A transmission observation image of the anti-glare film is taken using an optical microscope. The magnification is preferably 500 to 2000 times.

[0199] (A2) Ten random particles are extracted from the observed image, and the particle size of each particle is calculated. The particle size is measured as the distance between two random parallel straight lines in a combination of two straight lines that are the longest when the cross section of the particle is sandwiched between the two straight lines.

[0200] (A3) The same operation is performed five times on observation images of other screens of the same sample, and the value obtained by averaging the numerical values ​​of the particle diameters of 50 in total is taken as the average particle diameter of the particles.

[0201] The primary particle size of the inorganic fine particles forming the agglomerates can be measured according to the measurement methods (B1) to (B3) for hollow silica particles and non-hollow silica particles described below.

[0202] The coefficient of variation of the particle size of the particles is preferably 13% or less, more preferably 12% or less, and even more preferably 11% or less.

[0203] By setting the coefficient of variation of the particle size to 13% or less, it is possible to suppress the irregularities of the antiglare layer from becoming steep, and it is easy to set the average Δd to 40.0 nm or less.

[0204] The coefficient of variation of the particle size can be obtained, for example, from the following parameters and the following formula: the standard deviation calculated from the 50 particles used in the calculation of the average particle size in (A1) to (A3) above and the average particle size.

[0205] Coefficient of variation (%) = (standard deviation / average particle size) × 100

[0206] As for the particles, either organic particles or inorganic particles can be used, and organic particles are preferred for easy dispersion control. In addition, as for the particles, two or more particles having different materials can be used in combination, or two or more particles having different average particle diameters can be used in combination.

[0207] Examples of the organic particles include particles made of polymethyl methacrylate, polyacrylic acid-styrene copolymer, melamine resin, polycarbonate, polystyrene, polyvinyl chloride, benzoguanamine-melamine-formaldehyde condensate, silicone, fluorine-based resin, polyester-based resin, and the like.

[0208] Examples of the inorganic particles include particles composed of silica, alumina, zirconia, titania, and the like.

[0209] The shape of the particles may be spherical, elliptical, or irregular, with spherical shapes being preferred. Spherical particles can prevent the uneven shape of the antiglare layer from becoming steep, and can easily make the average Δd less than 40.0 nm.

[0210] The content of the particles is preferably 0.1 to 7.5 parts by mass, more preferably 0.8 to 6.0 parts by mass, and further preferably 1.0 to 5.0 parts by mass, relative to 100 parts by mass of the binder resin.

[0211] By making the content of the particles more than 0.1 parts by mass, it is possible to easily make the anti-glare property good. In addition, by making the content of the particles less than 7.5 parts by mass, it is possible to suppress the situation where the concavo-convex shape of the anti-glare layer becomes steep due to excessive aggregation of the particles, and it is easy to make the average of Δd less than 40.0nm.

[0212] The preferred range of the particle content relative to 100 parts by mass of the binder resin can be listed as 0.1 parts by mass or more and 7.5 parts by mass or less, 0.1 parts by mass or more and 6.0 parts by mass or less, 0.1 parts by mass or more and 5.0 parts by mass or less, 0.8 parts by mass or more and 7.5 parts by mass or less, 0.8 parts by mass or more and 6.0 parts by mass or less, 0.8 parts by mass or more and 5.0 parts by mass or less, 1.0 parts by mass or more and 7.5 parts by mass or less, 1.0 parts by mass or more and 6.0 parts by mass or less, and 1.0 parts by mass or more and 5.0 parts by mass or less.

[0213] The average film thickness of the antiglare layer is preferably 1 μm or more and 10 μm or less, more preferably 3 μm or more and 8 μm or less, and further preferably 4 μm or more and 6 μm or less.

[0214] The preferred range of the average film thickness of the anti-glare layer can be listed as 1 μm or more and 10 μm or less, 1 μm or more and 8 μm or less, 1 μm or more and 6 μm or less, 3 μm or more and 10 μm or less, 3 μm or more and 8 μm or less, 3 μm or more and 6 μm or less, 4 μm or more and 10 μm or less, 4 μm or more and 8 μm or less, and 4 μm or more and 6 μm or less.

[0215] The average film thickness of each layer constituting the anti-glare anti-reflection member, such as the anti-glare layer and the low refractive index layer, can be calculated from, for example, 20 random locations of a cross-sectional photograph of the anti-glare anti-reflection member based on a "scanning transmission electron microscope (STEM)", but the 20 locations are selected so that there is no deviation in the locations.

[0216] The acceleration voltage and magnification of STEM can be set according to the layer to be measured. For example, in the case of an anti-glare layer, it is preferred that the acceleration voltage of STEM is 10 kV or more and 30 kV or less, and the magnification of STEM is 1000 or more and 7000 or less.

[0217] When the film thickness of the antiglare layer is defined as T and the average particle size of the particles is defined as D, D / T is preferably 0.20 to 0.80, more preferably 0.30 to 0.70, and further preferably 0.40 to 0.60.

[0218] By making D / T be the above range, appropriate concavity and convexity can be produced at the position with particles and the position without particles. It should be noted that the concavity and convexity of the anti-glare layer is produced, for example, by the difference in the shrinkage of the binder resin at the position with particles and the position without particles. This is because, compared with the position with particles, the shrinkage at the position without particles is larger, so it is easy to become a concave portion.

[0219] Preferred ranges of D / T include 0.20 to 0.80, 0.20 to 0.70, 0.20 to 0.60, 0.30 to 0.80, 0.30 to 0.70, 0.30 to 0.60, 0.40 to 0.80, 0.40 to 0.70, and 0.40 to 0.60.

[0220] The anti-glare layer may contain a leveling agent such as a fluorine-based leveling agent, a silicone-based leveling agent, or a fluorine-based silicone-based leveling agent.

[0221] The content of the leveling agent is preferably 0.01 to 0.20 parts by mass, more preferably 0.02 to 0.10 parts by mass, and further preferably 0.03 to 0.07 parts by mass, relative to 100 parts by mass of the binder resin.

[0222] The preferred range of the content of the leveling agent relative to 100 parts by mass of the binder resin is 0.01 parts by mass or more and 0.20 parts by mass or less, 0.01 parts by mass or more and 0.10 parts by mass or less, 0.01 parts by mass or more and 0.07 parts by mass or less, 0.02 parts by mass or more and 0.20 parts by mass or less, 0.02 parts by mass or more and 0.10 parts by mass or less, 0.02 parts by mass or more and 0.07 parts by mass or less, 0.03 parts by mass or more and 0.20 parts by mass or less, 0.03 parts by mass or more and 0.10 parts by mass or less, and 0.03 parts by mass or more and 0.07 parts by mass or less.

[0223] The anti-glare layer may contain other additives within a range that does not hinder the effects of the present disclosure. Examples of the additives include ultraviolet absorbers, antioxidants, and light stabilizers.

[0224] The refractive index of the anti-glare layer is preferably 1.48 or more and 1.62 or less, more preferably 1.50 or more and 1.54 or less, and further preferably 1.52 or more and 1.53 or less. By setting the refractive index of the anti-glare layer to the above range and setting the refractive index of the low-refractive index layer to the range described later, it is possible to easily suppress the coloring when observing from an oblique direction, and it is possible to easily reduce the visual reflectivity Y value.

[0225] Preferred ranges of the refractive index of the antiglare layer include 1.48 to 1.62, 1.48 to 1.54, 1.48 to 1.53, 1.50 to 1.62, 1.50 to 1.54, 1.50 to 1.53, 1.52 to 1.62, 1.52 to 1.54, and 1.52 to 1.53.

[0226] Solvents

[0227] In the coating liquid for an antiglare layer, a solvent is usually used in order to adjust the viscosity or to dissolve or disperse each component.

[0228] As for the solvent, for example, ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ethers such as dioxane and tetrahydrofuran; aliphatic hydrocarbons such as hexane; alicyclic hydrocarbons such as cyclohexane; aromatic hydrocarbons such as toluene and xylene; halogenated carbons such as dichloromethane and dichloroethane; esters such as methyl acetate, ethyl acetate, and butyl acetate; alcohols such as isopropyl alcohol, butanol, and cyclohexanol; cellosolves such as methyl cellosolve and ethyl cellosolve; glycol ethers such as propylene glycol monomethyl ether acetate; cellosolve acetates; sulfoxides such as dimethyl sulfoxide; amides such as dimethylformamide and dimethylacetamide, etc., and mixtures thereof are also possible.

[0229] If the time required for drying the solvent in the anti-glare layer coating liquid is too long, the particles will be excessively aggregated, thereby increasing the average Δd. In addition, if the time required for drying the solvent in the anti-glare layer coating liquid is too short, the particles will not be sufficiently aggregated, thereby decreasing the average Δd. Therefore, for the solvent in the anti-glare layer coating liquid, it is preferred to use a mixture of a solvent having a fast evaporation rate and a solvent having a slow evaporation rate.

[0230] In this specification, a solvent with a fast evaporation rate refers to a solvent having an evaporation rate of 120 or more when the evaporation rate of butyl acetate is set to 100. In addition, in this specification, a solvent with a slow evaporation rate refers to a solvent having an evaporation rate of less than 120 when the evaporation rate of butyl acetate is set to 100.

[0231] Among the solvents in the anti-glare layer coating solution, the evaporation rate of the solvent with a fast evaporation rate is preferably 150 to 500, more preferably 250 to 450, and even more preferably 300 to 400. Examples of the solvent with a fast evaporation rate include methyl isobutyl ketone with an evaporation rate of 160 and methyl ethyl ketone with an evaporation rate of 370.

[0232] Among the solvents in the anti-glare layer coating solution, the evaporation rate of the solvent with a slow evaporation rate is preferably 15 to 110, more preferably 30 to 100, and even more preferably 50 to 95. Examples of the solvent with a slow evaporation rate include cyclopentanone with an evaporation rate of 90, propylene glycol monomethyl ether acetate with an evaporation rate of 44, propylene glycol monomethyl ether propionate with an evaporation rate of 19, and cyclohexanone with an evaporation rate of 32.

[0233] In the solvent of the antiglare layer coating liquid, the mass ratio of the solvent having a fast evaporation rate to the solvent having a slow evaporation rate is preferably 50 / 50 to 90 / 10, more preferably 60 / 40 to 80 / 20.

[0234] The antiglare layer coating liquid preferably contains a solvent at a solid content concentration of 30% by mass or more and 70% by mass or less, and more preferably contains a solid content concentration of 40% by mass or more and 60% by mass or less.

[0235] When the anti-glare layer-forming coating liquid is applied and dried, it is preferable to control the drying conditions.

[0236] The drying conditions can be controlled, for example, by the drying temperature, the drying time, and the wind speed in the dryer. The drying temperature is preferably 50°C or more and 120°C or less, more preferably 60°C or more and 100°C or less, and further preferably 70°C or more and 90°C or less. The drying time is preferably 10 seconds or more and 50 seconds or less, and more preferably 20 seconds or more and 40 seconds or less. The drying wind speed is preferably 0.2 m / s or more and 50 m / s or less, more preferably 0.5 m / s or more and 30 m / s or less, and further preferably 1 m / s or more and 25 m / s or less.

[0237] The direction of the drying air is preferably substantially horizontal to the substrate, and more preferably substantially horizontal to the conveyance direction of the substrate.

[0238] In order to control the surface shape of the anti-glare layer by drying, when irradiating with ionizing radiation during the formation of the anti-glare layer, it is preferred to perform the irradiation after the coating liquid is dried.

[0239] 《Surface roughness of anti-glare layer》

[0240] The surface roughness of the antiglare layer is preferably within a predetermined range.

[0241] For example, the arithmetic mean roughness Ra of the antiglare layer is preferably 0.03 μm or more and 0.20 μm or less, more preferably 0.04 μm or more and 0.09 μm or less, and further preferably 0.05 μm or more and 0.07 μm or less.

[0242] The surface roughness of the anti-glare layer refers to the surface roughness in a state where other layers such as a low-refractive index layer are not formed on the anti-glare layer.

[0243] The surface roughness of the antiglare layer is an average value obtained by measuring 10 locations.

[0244] Preferred ranges of Ra on the surface of the antiglare layer include 0.03 μm to 0.20 μm, 0.03 μm to 0.09 μm, 0.03 μm to 0.07 μm, 0.04 μm to 0.20 μm, 0.04 μm to 0.09 μm, 0.04 μm to 0.07 μm, 0.05 μm to 0.20 μm, 0.05 μm to 0.09 μm, and 0.05 μm to 0.07 μm.

[0245] In this specification, Ra is a parameter obtained by expanding Ra as a two-dimensional roughness parameter recorded in JIS B0601:1994 into three dimensions. If the orthogonal coordinate axes X and Y are placed on the reference plane, the roughness surface is set to Z (x, y), and the size of the reference plane is set to Lx and Ly, Ra is calculated by the following formula (1). In the following formula (1), A = Lx × Ly. In this specification, Ra refers to the value measured by setting the cutoff value to Ly / 4 (mm). Wherein, Lx < Lx.

[0246] [Number 1]

[0247]

[0248] <Low refractive index layer>

[0249] The low refractive index layer is a layer located on the surface of the anti-glare layer opposite to the substrate. The low refractive index layer is preferably arranged so as to form the surface of the anti-glare antireflection member.

[0250] The refractive index of the low refractive index layer is preferably 1.10 to 1.48, more preferably 1.20 to 1.45, more preferably 1.26 to 1.40, more preferably 1.28 to 1.38, and more preferably 1.30 to 1.32.

[0251] It should be noted that, in this specification, the refractive index refers to the refractive index at a wavelength of 589.3 nm.

[0252] Preferred ranges of the refractive index of the low refractive index layer include 1.10 to 1.48, 1.10 to 1.45, 1.10 to 1.40, 1.10 to 1.38, 1.10 to 1.32, 1.20 to 1.48, 1.20 to 1.45, 1.20 to 1.40, 1.20 to 1.38, 1.20 to 1.32, 1.26 to 1.48, 1.26 to 1.45. Below, 1.26 or more and 1.40 or less, 1.26 or more and 1.38 or less, 1.26 or more and 1.32 or less, 1.28 or more and 1.48 or less, 1.28 or more and 1.45 or less, 1.28 or more and 1.40 or less, 1.28 or more and 1.38 or less, 1.28 or more and 1.32 or less, 1.30 or more and 1.48 or less, 1.30 or more and 1.45 or less, 1.30 or more and 1.40 or less, 1.30 or more and 1.38 or less, 1.30 or more and 1.32 or less.

[0253] The average thickness of low refractive index layer is preferably more than 80nm and below 130nm, more preferably more than 85nm and below 110nm, further preferably more than 90nm and below 105nm.In addition, the average thickness of low refractive index layer is preferably greater than the average particle diameter of hollow particle and non-hollow particle etc., the particle contained in the low refractive index layer.

[0254] The average preferred range of the film thickness of the low refractive index layer can be listed as 80nm or more and 130nm or less, 80nm or more and 110nm or less, 80nm or more and 105nm or less, 85nm or more and 130nm or less, 85nm or more and 110nm or less, 85nm or more and 105nm or less, 90nm or more and 130nm or less, 90nm or more and 110nm or less, 90nm or more and 105nm or less.

[0255] The anti-glare layer may or may not contact the low-refractive index layer, but preferably contacts to form. In other words, preferably other layers such as high-refractive index layer are not sandwiched between the anti-glare layer and the low-refractive index layer. By being set to the above-mentioned structure, the colored when observing from the oblique direction can be easily suppressed.

[0256] When another layer is interposed between the anti-glare layer and the low refractive index layer, it is preferable that the refractive index of the other layer be within the above-mentioned appropriate range of the refractive index of the anti-glare layer.

[0257] The method of forming the low refractive index layer can be roughly divided into a wet method and a dry method. In the dry method, it is difficult to give a difference in the film thickness of the low refractive index layer, so the wet method is preferred.

[0258] As the wet method, there can be cited a method of forming by a sol-gel method using a metal alkoxide or the like, a method of forming by coating a low-refractive-index resin such as a fluororesin, and a method of forming by coating a low-refractive-index layer-forming coating liquid containing a binder resin composition and low-refractive-index particles. Among them, forming by a low-refractive-index layer-forming coating liquid containing low-refractive-index particles in a binder resin composition is preferred.

[0259] The low refractive index layer preferably contains a binder resin and particles. In addition, the particles preferably contain hollow particles and non-hollow particles. That is, the low refractive index layer more preferably contains a binder resin, hollow particles, and non-hollow particles.

[0260] Hollow Particles and Non-Hollow Particles

[0261] The material of the hollow particles and the non-hollow particles can be any inorganic compound or organic compound such as silicon dioxide and magnesium fluoride, but silicon dioxide is preferred to ensure low refractive index and strength. Hereinafter, hollow particles and non-hollow particles will be described with hollow silica particles and non-hollow silica particles as the center.

[0262] Hollow silica particles refer to particles having an outer shell layer composed of silica, and the inside of the particles surrounded by the outer shell layer is hollow, and air is contained in the hollow. Hollow silica particles are particles that contain air, and thus, the refractive index is reduced in proportion to the occupancy rate of the gas compared to the original refractive index of silica. Non-hollow silica particles refer to particles that are not hollow inside like hollow silica particles. Non-hollow silica particles are, for example, solid silica particles.

[0263] The shapes of the hollow silica particles and non-hollow silica particles are not particularly limited, and may be a true sphere, a rotational ellipsoid, or a substantially spherical shape such as a polyhedron that can approximate a sphere, etc. Of these, a true sphere, a rotational ellipsoid, or a substantially spherical shape is preferred in consideration of scratch resistance.

[0264] Hollow silica particles contain air inside, so they can play a role in reducing the refractive index of the entire low refractive index layer. By using hollow silica particles with a large particle size that has improved the air ratio, the refractive index of the low refractive index layer can be further reduced. On the other hand, hollow silica particles have a tendency to have poor mechanical strength. Especially in the case of hollow silica particles with a large particle size that has improved the air ratio, there is a tendency to easily cause the scratch resistance of the low refractive index layer to decrease.

[0265] The non-hollow silica particles are preferably present on the side of the low refractive index layer opposite to the anti-glare layer, and more preferably dispersed throughout the low refractive index layer. The presence of the non-hollow silica particles as described above can easily improve the scratch resistance of the low refractive index layer.

[0266] The average particle diameter of the hollow silica particles and the average particle diameter of the non-hollow silica particles are preferably set so that the hollow silica particles are close to each other and the non-hollow particles enter between the hollow silica particles.

[0267] Specifically, the ratio of the average particle size of the non-hollow silica particles to the average particle size of the hollow silica particles is preferably 0.29 or less, more preferably 0.27 or less. By making the average particle size of the non-hollow silica particles / the average particle size of the hollow silica particles be the above range, thus, in the film thickness direction of the low refractive index layer, the hollow silica particles and the non-hollow silica particles are easily and evenly dispersed, and it is easy to make the scratch resistance good. It should be noted that the ratio of the average particle size is preferably 0.05 or more, more preferably 0.15 or more.

[0268] Preferred ranges of the average particle size ratio include 0.05 to 0.29, 0.05 to 0.27, 0.15 to 0.29, and 0.15 to 0.27.

[0269] In consideration of optical properties and mechanical strength, the average particle size of the hollow silica particles is preferably 20 nm to 100 nm, more preferably 30 nm to 90 nm, and still more preferably 40 nm to 80 nm.

[0270] Regarding the preferred range of the average particle size of the hollow silica particles, there are 20 nm or more and 100 nm or less, 20 nm or more and 90 nm or less, 20 nm or more and 80 nm or less, 30 nm or more and 100 nm or less, 30 nm or more and 90 nm or less, 30 nm or more and 80 nm or less, 40 nm or more and 100 nm or less, 40 nm or more and 90 nm or less, and 40 nm or more and 80 nm or less.

[0271] If the dispersion is considered while preventing the aggregation of the non-hollow silica particles, the average particle size of the non-hollow silica particles is preferably 0.5 nm or more and smaller than the average particle size of the hollow silica particles. In addition, the average particle size of the non-hollow silica particles is preferably 0.5 nm or more and 20 nm or less, and more preferably 5 nm or more and 20 nm or less.

[0272] The average particle diameter of the hollow silica particles and the non-hollow silica particles can be calculated, for example, by the following operations (B1) to (B3).

[0273] (B1) Photographing a cross section of the antiglare antireflection member containing particles using TEM or STEM The accelerating voltage of TEM or STEM is preferably set to 10 kV to 30 kV, and the magnification is preferably set to 50,000 to 300,000 times.

[0274] (B2) Ten random particles are extracted from the observed image, and the particle size of each particle is calculated. The particle size is measured as the distance between two random parallel straight lines in a combination of two straight lines that are the longest when the cross section of the particle is sandwiched between the two straight lines.

[0275] (B3) The same operation is performed five times on observation images of other screens of the same sample, and the value obtained by averaging the total number of 50 is taken as the average particle size of the particles.

[0276] It is preferred that the surfaces of the hollow silica particles and the non-hollow silica particles be coated with a silane coupling agent. The silane coupling agent is preferably a silane coupling agent having a (meth)acryloyl group or an epoxy group.

[0277] By subjecting the silica particles to a surface treatment based on a silane coupling agent, the affinity of the silica particles to the binder resin is improved, and the aggregation of the silica particles is not easily generated. Therefore, the dispersion of the silica particles is easily uniform. In addition, by using a silane coupling agent to improve the affinity of the silica particles to the binder resin, the resistance of the low refractive index layer in a wet state formed on the convex portion of the anti-glare layer to flow down to the flat portion side of the anti-glare layer is increased, and the situation where the average of Δd becomes too large can be easily suppressed.

[0278] The more the content of hollow silica particles, the higher the filling rate of the hollow silica particles in the binder resin, the lower the refractive index of the low refractive index layer. In addition, the more the content of hollow silica particles, the higher the viscosity of the low refractive index layer coating solution, the more the resistance of the low refractive index layer formed on the convex portion of the anti-glare layer when flowing down to the flat portion side of the anti-glare layer increases, so that the average of Δd can be easily suppressed from becoming too large. Therefore, relative to 100 parts by mass of the binder resin, the content of the hollow silica particles is preferably 100 parts by mass or more, more preferably 130 parts by mass or more.

[0279] On the other hand, if the content of the hollow silica particles is too much, there is a tendency for the mechanical strength such as the scratch resistance of the low refractive index layer to decrease. In addition, if the content of the hollow silica particles is too much, the viscosity of the low refractive index layer coating solution increases excessively, and there is a tendency for the average Δd to become too small. Therefore, the content of the hollow silica particles is preferably 300 parts by mass or less, more preferably 200 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0280] Preferred ranges of the content of the hollow silica particles relative to 100 parts by mass of the binder resin include 100 parts by mass to 300 parts by mass, 100 parts by mass to 200 parts by mass, 130 parts by mass to 300 parts by mass, and 130 parts by mass to 200 parts by mass.

[0281] If the content of non-hollow silica particles is less, even if non-hollow silica particles are present on the surface of the low-refractive index layer, sometimes the hardness rise will not be affected. In addition, the more the content of non-hollow silica particles, the more the viscosity of the low-refractive index layer coating solution rises, and the resistance of the low-refractive index layer in a wet state formed on the convex portion of the anti-glare layer to the flat portion side of the anti-glare layer increases, so that the average of Δd can be easily suppressed from becoming too large. In addition, the more the content of non-hollow silica particles, the more it can reduce the impact of the uneven shrinkage caused by the polymerization of the binder resin, and the easier it is to adjust the average of Δd. Therefore, relative to 100 parts by mass of binder resin, the content of non-hollow silica particles is preferably more than 50 parts by mass, more preferably more than 60 parts by mass.

[0282] On the other hand, if the content of the non-hollow silica particles is too much, the viscosity of the low refractive index layer coating solution increases excessively, and there is a tendency for the average Δd to become too small. Therefore, the content of the non-hollow silica particles is preferably 150 parts by mass or less, more preferably 100 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0283] Preferred ranges of the content of the non-hollow silica particles relative to 100 parts by mass of the binder resin include 50 parts by mass to 150 parts by mass, 50 parts by mass to 100 parts by mass, 60 parts by mass to 150 parts by mass, and 60 parts by mass to 100 parts by mass.

[0284] 《Binder resin》

[0285] The binder resin of the low refractive index layer preferably comprises a cured product of a curable resin composition. The cured product of the curable resin composition includes a cured product of a thermosetting resin composition and a cured product of an ionizing radiation curable resin composition. In order to obtain better mechanical strength, a cured product of an ionizing radiation curable resin composition is preferred.

[0286] As the thermosetting resin composition and ionizing radiation curing resin composition of the low refractive index layer, the same composition as the composition exemplified in the anti-glare layer can be listed. Among them, the ionizing radiation curing resin composition is preferred. That is, the binder resin of the low refractive index layer preferably includes the cured product of the ionizing radiation curing resin composition.

[0287] As the ionizing radiation curable resin composition of the low refractive index layer, preferably a multifunctional (meth) acrylate compound, preferably a multifunctional (meth) acrylate oligomer. That is, the binder resin of the low refractive index layer preferably comprises a cured product of a multifunctional (meth) acrylate oligomer. The cured product of the multifunctional (meth) acrylate oligomer can make the surface hardness of the anti-glare anti-reflection component good, while being able to suppress the excessive curing shrinkage of the low refractive index layer, and easily adjusting the average of Δd. In addition, the multifunctional (meth) acrylate oligomer can appropriately improve the viscosity of the low refractive index layer coating solution, and easily suppress the situation where the average of Δd becomes too large.

[0288] The ratio of the cured product of the polyfunctional (meth)acrylate oligomer to the total binder resin of the low refractive index layer is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and further preferably 100% by mass.

[0289] In addition, the low refractive index layer may contain a binder resin other than the cured product of the multifunctional (meth)acrylate oligomer within a range not hindering the effects of the present disclosure.

[0290] Examples of the polyfunctional (meth)acrylate oligomer include (meth)acrylate polymers such as urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, and polyether (meth)acrylate.

[0291] The weight average molecular weight of the oligomer of the polyfunctional (meth)acrylate compound is preferably 500 or more and 5,000 or less, and more preferably 1,000 or more and 3,000 or less.

[0292] By making the weight average molecular weight of the oligomer more than 500, the excessive curing shrinkage of the low refractive index layer can be suppressed, and the average of Δd can be easily adjusted. In addition, by setting the weight average molecular weight of the oligomer to the above-mentioned range, the viscosity of the low refractive index layer coating solution can be easily adjusted to a range that is not too low and not too high, and the average of Δd can be easily set to more than 7.0nm and below 40.0nm.

[0293] Preferred ranges of the weight average molecular weight of the oligomer of the polyfunctional (meth)acrylate compound include 500 to 5,000, 500 to 3,000, 1,000 to 5,000, and 1,000 to 3,000.

[0294] The binder resin of the low refractive index layer preferably contains the same components as the binder resin of the anti-glare layer. According to the above-mentioned configuration, the affinity between the anti-glare layer and the low refractive index layer increases, and the resistance of the low refractive index layer in a wet state formed on the convex portion of the anti-glare layer to flow down to the flat portion side of the anti-glare layer increases, which can easily suppress the situation where the average of Δd becomes too large.

[0295] The proportion of the same component as the binder resin of the anti-glare layer relative to the total amount of the binder resin of the low refractive index layer is preferably 30% by mass or more, more preferably 50% by mass or more, further preferably 70% by mass or more, and further preferably 90% by mass or more.

[0296] The low refractive index layer may contain a leveling agent such as a fluorine-based leveling agent, a silicone-based leveling agent, or a fluorine-based silicone-based leveling agent.

[0297] The content of the leveling agent is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, and further preferably 0.3 to 3 parts by mass, relative to 100 parts by mass of the binder resin.

[0298] The preferred range of the content of the leveling agent relative to 100 parts by mass of the binder resin can be listed as 0.1 parts by mass or more and 10 parts by mass or less, 0.1 parts by mass or more and 5 parts by mass or less, 0.1 parts by mass or more and 3 parts by mass or less, 0.2 parts by mass or more and 10 parts by mass or less, 0.2 parts by mass or more and 5 parts by mass or less, 0.2 parts by mass or more and 3 parts by mass or less, 0.3 parts by mass or more and 10 parts by mass or less, 0.3 parts by mass or more and 5 parts by mass or less, and 0.3 parts by mass or more and 3 parts by mass or less.

[0299] When the ionizing radiation curable compound of the binder resin forming the low refractive index layer is an ultraviolet curable compound, the ionizing radiation curable composition preferably contains additives such as a photopolymerization initiator and a photopolymerization accelerator.

[0300] Examples of the photopolymerization initiator include at least one selected from acetophenone, benzophenone, α-hydroxyalkylphenone, Michler's ketone, benzoin, benzyl dimethyl ketal, benzoyl benzoate, α-acyl oxime ester, anthraquinone, haloketone, thioxanthone, etc. Among them, α-hydroxyalkylphenone is preferred.

[0301] The photopolymerization accelerator can reduce polymerization hindrance caused by air during curing to accelerate the curing rate, and examples thereof include at least one selected from isopentyl p-dimethylaminobenzoate, ethyl p-dimethylaminobenzoate, and the like.

[0302] The low refractive index layer may contain other additives within a range that does not hinder the effects of the present disclosure. Examples of the additives include ultraviolet absorbers, antioxidants, and light stabilizers.

[0303] Solvents

[0304] In the low refractive index layer coating liquid, a solvent is usually used to adjust the viscosity or to dissolve or disperse the components.

[0305] The solvent of the low-refractive-index layer coating solution may be the same solvent as exemplified as the solvent of the anti-glare layer coating solution.

[0306] If the time required for drying the solvent in the low refractive index layer coating solution is too long, there is a situation where the low refractive index layer in a wet state formed on the convex portion of the anti-glare layer excessively flows down to the flat portion side of the anti-glare layer, so that the average of Δd becomes too large. In addition, if the time required for drying the solvent in the low refractive index layer coating solution is too short, there is a situation where the amount of the low refractive index layer in a wet state formed on the convex portion of the anti-glare layer flowing down to the flat portion side of the anti-glare layer is insufficient, so that the average of Δd becomes too small. Therefore, for the solvent in the low refractive index layer coating solution, it is preferred to mix a solvent with a fast evaporation rate and a solvent with a slow evaporation rate for use.

[0307] Among the solvents in the low refractive index layer coating solution, the evaporation rate of the solvent with a fast evaporation rate is preferably 125 to 300, more preferably 130 to 250, and even more preferably 140 to 200. Examples of the solvent with a fast evaporation rate include methyl isobutyl ketone having an evaporation rate of 160.

[0308] Among the solvents in the low refractive index layer coating solution, the evaporation rate of the solvent with a slow evaporation rate is preferably 20 or more and 90 or less, more preferably 25 or more and 80 or less, and further preferably 30 or more and 60 or less. Examples of the solvent with a slow evaporation rate include propylene glycol monomethyl ether acetate having an evaporation rate of 44.

[0309] In the solvent of the low refractive index layer coating liquid, the mass ratio of the solvent having a fast evaporation rate to the solvent having a slow evaporation rate is preferably 50 / 50 to 90 / 10, more preferably 60 / 40 to 80 / 20.

[0310] The low refractive index layer coating liquid preferably contains a solvent at a solid content concentration of 1% to 10% by mass, and more preferably 3% to 7% by mass.

[0311] When the low refractive index layer coating liquid is applied and dried, it is preferable to control the drying conditions.

[0312] The drying conditions can be controlled, for example, by the drying temperature, drying time and wind speed in the dryer. The drying temperature is preferably 40°C to 100°C, more preferably 45°C to 80°C, and further preferably 50°C to 70°C. The drying time is preferably 10 seconds to 50 seconds, more preferably 20 seconds to 40 seconds. The drying wind speed is preferably 0.2 m / s to 50 m / s, more preferably 0.5 m / s to 30 m / s, and further preferably 1 m / s to 25 m / s.

[0313] In addition, the direction of the drying wind is preferably substantially horizontal to the substrate, more preferably substantially horizontal in a manner opposite to the conveying direction of the substrate. On the other hand, when the direction of the drying wind is perpendicular to the substrate, the proportion of the low refractive index layer in a wet state formed on the convex portion of the anti-glare layer flowing down toward the flat portion of the anti-glare layer tends to become excessive, and there is a tendency for the average of Δd to become too large.

[0314] In addition, when irradiating with ionizing radiation during the formation of the low refractive index layer, it is preferable to perform irradiation after the coating liquid is dried in order to ensure the fluidity of the low refractive index layer in a wet state.

[0315] Furthermore, in order to easily make the average Δd not less than 7.0 nm and not more than 40.0 nm, it is preferable to include a step of heating the substrate side during the period from the completion of the formation of the antiglare layer on the substrate to the completion of the formation of the low refractive index layer.

[0316] If the drying time of the solvent contained in the low refractive index layer in the wet state is too long, there is a situation where the average of Δd becomes too large. The drying speed of the solvent can be adjusted according to the type and drying conditions of the solvent. But, if considering environmental burden, the solubility of the adhesive resin with the adhesion of the anti-glare layer, the low refractive index layer, etc., the type of solvent can be restricted sometimes. In addition, if considering the heat resistance of the substrate, etc., the drying conditions can be restricted sometimes. Therefore, it is preferred to adjust the drying time by other means except the type and drying conditions of the solvent.

[0317] As other means, the above-mentioned process of heating from the substrate side can be listed. If the above-mentioned process is provided, the temperature of the surface of the anti-glare layer on which the coating liquid for the low refractive index layer is applied will rise, so the drying time of the coating liquid for the low refractive index layer can be shortened. Regarding the means of heating from the substrate side, for example, means of heating rollers such as conveying rollers and pressure-bonding rollers can be listed. At this time, the substrate temperature is preferably set to above 30°C and below 55°C, and more preferably set to above 35°C and below 50°C. In addition, at the moment of applying the coating liquid for the low refractive index layer, the substrate temperature is preferably in the above-mentioned range. In addition, the substrate temperature and the temperature of the drying wind preferably satisfy the relationship of "substrate temperature < temperature of the drying wind".

[0318] "Film Thickness Difference"

[0319] Regarding the anti-glare anti-reflection component disclosed in the present invention, when the difference in the film thickness of the low refractive index layer in any 2 mm×2 mm area of ​​the anti-glare anti-reflection component is defined as Δd, it is necessary to make the average of Δd be greater than 7.0 nm and less than 40.0 nm. As described above, Δd refers to the difference in the film thickness of the low refractive index layer in the finished state of the anti-glare anti-reflection component. The technical significance of the average of Δd is explained below.

[0320] Usually, for low refractive index layer, the wavelength that people's visual sensitivity is high is that the reflectivity of the light of 550nm in the front direction decreases to design film thickness.But, in the oblique direction, the distance of the light by low refractive index layer increases, and film thickness increases in fact.Therefore, in the common low refractive index layer designed in the mode that the reflectivity of the light of 550nm in the front direction decreases to design, the reflectivity of oblique direction cannot be reduced.Particularly, in the low refractive index layer of common design, the reflectivity of the light in the red wavelength region with longer wavelength becomes extremely high.Therefore, in the low refractive index layer of common design, the coloring when observing from oblique direction cannot be suppressed.

[0321] In the present disclosure, by setting the average of Δd to more than 7.0nm and giving the low refractive index layer a film thickness difference, it is possible to suppress the influence of the film thickness of the low refractive index layer substantially increasing in the oblique direction, thereby suppressing the coloring when observed from the oblique direction. It is important to grasp it not as the film thickness of the microscopic region, but as the average of the film thickness of the macroscopic region of the size that can be recognized by people. For the average of the film thickness of the macroscopic region of the size that can be recognized by people, by setting the average of Δd to more than 7.0nm, the rate of increase in the oblique direction can be suppressed. Therefore, by setting the average of Δd to more than 7.0nm, the coloring when observed from the oblique direction can be suppressed.

[0322] The average of Δd is preferably 10.0 nm or more, more preferably 15.0 nm or more, and further preferably 20.0 nm or more.

[0323] However, when the average of Δd is too large, the reflectivity becomes different locally, so bright spots are seen. In the present disclosure, the film thickness difference of the low refractive index layer is suppressed by setting the average of Δd to 40.0nm or less, thereby suppressing the situation of seeing bright spots. The average of Δd is preferably 35.0nm or less, more preferably 33.0nm or less, and further preferably 30.0nm or less.

[0324] Preferred ranges of the average of Δd include 7.0 nm to 35.0 nm, 7.0 nm to 33.0 nm, 7.0 nm to 30.0 nm, 10.0 nm to 40.0 nm, 10.0 nm to 35.0 nm, 10.0 nm to 33.0 nm, 10.0 nm to 30.0 nm, 15.0 nm to 40.0 nm, 15.0 nm to 35.0 nm, 15.0 nm to 33.0 nm, 15.0 nm to 30.0 nm, 20.0 nm to 40.0 nm, 20.0 nm to 35.0 nm, 20.0 nm to 33.0 nm, and 20.0 nm to 30.0 nm.

[0325] The measurement area of ​​Δd is set to 2 mm×2 mm in consideration of the following factors: it is a range that is difficult to exceed the measurement spot of the reflectance; and it is a size that can be sufficiently discriminated by humans.

[0326] In addition, regarding the measurement spot of reflectivity, in the examples described later, the size of the measurement spot at an incident angle of 5 degrees is 50.2 mm. 2 , the size of the measurement spot at an incident angle of 60 degrees is 100.0 mm 2The size of the measurement spot changes depending on the angle because the measurement is performed by projecting light that has passed through a mask of a predetermined size onto an inclined sample. In the examples described below, a mask of 5 mm×10 mm in size is used as the mask.

[0327] Δd indicating the difference in film thickness of the low refractive index layer in an arbitrary region of 2 mm×2 mm can be measured, for example, as shown in the following z1 to z10.

[0328] (z1) Sample A1 is prepared by cutting the anti-glare anti-reflection component into a 2 mm wide strip. Hereinafter, the direction of the 2 mm width of sample A1 is referred to as the short side direction, and the direction orthogonal to the short side direction is referred to as the long side direction. In addition, considering the roughness near the cut surface of sample A1, sampling can also be performed with a margin in the short side direction. That is, if the area to be observed is 2 mm, the short side direction of sample A1 can also be more than 3 mm and less than 4 mm.

[0329] Alternatively, a sample prepared by bonding the substrate-side surface of the antiglare antireflection member to a plastic plate may be used as sample A1. A laminated body is prepared and the laminated body is cut as described above.

[0330] (z2) The surface shape of the low refractive index layer side of sample A1 is measured by a white interference surface shape measuring instrument. The measurement area is set to a 2mm×2mm area from the end of the short side direction of sample A1 to the area 2mm advanced. It should be noted that, considering that the short side and the end of the long side direction of sample A1 are relatively rough, the measurement area can also be set excluding the end, or the 2mm×2mm area can be selected from the 3mm×3mm area including the end.

[0331] (z3) Obtain height profiles in the short-side direction at four locations that are 400 nm, 800 nm, 1200 nm, and 1600 nm farther from the end of the short-side direction of the measurement region.

[0332] For example, Figure 3 It is a top view of sample A1. The range of the bold line represents the measurement area of ​​2 mm×2 mm, and the four dotted lines i, ii, iii, and iv correspond to the four short side directions of the height profile.

[0333] (z4) For the four height profiles, the peak point, which is the part with the highest elevation of the height profile, and the part with the lowest elevation of the height profile are determined respectively, and the distance L1 from the end of the long side direction of the sample A1 to the peak point and the distance L2 from the end of the long side direction of the sample A1 to the bottom are determined. In this specification, the “part with the lowest elevation of the height profile” is sometimes referred to as the “bottom”.

[0334] (z5) Prepare an embedded sample B1 by embedding the sample A1 with a resin.

[0335] (z6) The embedded sample B1 is cut in a direction parallel to the short side direction of the sample A1 to expose a vertical cross section of the sample A1 at a position 400 nm forward from the end of the short side direction of the measurement region of the sample A1.

[0336] (z7) A vertical cross section is observed using a scanning transmission electron microscope, and dmin, which indicates the film thickness of the low refractive index layer at a portion corresponding to the peak point, and dmax, which indicates the film thickness of the low refractive index layer at a portion corresponding to the bottom, are calculated.

[0337] (z8) Based on the difference between dmax and dmin, di indicating the difference in film thickness at a location 400 nm further from the end of the measurement region in the short-side direction is calculated.

[0338] (z9) The embedded sample B1 is cut in a direction parallel to the short side direction of the sample A1 to expose the vertical cross section of the sample A1 at the position 800nm, 1200nm and 1600nm from the end of the short side direction of the measurement area of ​​the sample A1, and the same operation as z7 to z8 is performed. Through this operation, d-ii, d-iii and d-iv representing the film thickness difference at the position 800nm, 1200nm and 1600nm from the end of the short side direction of the measurement area are calculated.

[0339] (z10) By averaging di, d-ii, d-iii and d-iv, Δd representing the difference in film thickness of the low refractive index layer in an arbitrary 2 mm × 2 mm area can be calculated.

[0340] The embedded sample can be obtained, for example, by placing a long strip of sample in a silicon embedding plate, pouring an embedding resin, and then curing the embedding resin, and then taking out the cut sample and the embedding resin that wrapped it from the silicon embedding plate, thereby obtaining the embedded sample. In the case of the epoxy resin manufactured by Struers, which is exemplified below, the above-mentioned curing step is preferably performed after being left at room temperature for 12 hours.

[0341] For example, the silicon embedding plate manufactured by Dosaka IEM Co., Ltd. is exemplified. The silicon embedding plate is sometimes also referred to as a silicon capsule. For example, the epoxy resin used for embedding can be a mixture of "Epofix" manufactured by Struers and "Epofix Curing Agent" manufactured by the same company at a ratio of 10:1.2.

[0342] The embedded sample is preferably cut with a diamond knife.

[0343] As an apparatus for cutting the embedded sample, for example, there is a product called "Ultra Microtome EM UC7" manufactured by Leica Micro Systems.

[0344] The “average of Δd” can be calculated by calculating Δd indicating the difference in film thickness of the low refractive index layer in an area of ​​2 mm×2 mm at 10 locations on the antiglare antireflection member and calculating it as the average value of the Δd at the 10 locations.

[0345] It should be noted that, among the Δd at the ten locations, the number of locations where the absolute value of Δd satisfies 7.0 nm or more and 40.0 nm or less is preferably 8 or more, more preferably 9 or more, and even more preferably 10.

[0346] <Physical Properties>

[0347] The antiglare antireflection member preferably has a visual reflectance Y value measured at a light incident angle of 5 degrees from the side having the low refractive index layer of 3.0% or less, more preferably 2.0% or less, and even more preferably 1.5% or less.

[0348] In the antiglare antireflection member of the present disclosure, the thickness of the low refractive index layer varies, so there is a limit to the reflectivity. Therefore, the lower limit of the visual reflectivity Y value is preferably 0.5% or more, more preferably 0.8% or more, and even more preferably 1.0% or more.

[0349] In this specification, the visual reflectance Y value refers to the visual reflectance Y value of the CIE1931 standard color system. The visual reflectance Y value can be calculated using spectrophotometry. As a spectrophotometer, for example, a spectrophotometer with the trade name "UV-3600plus" manufactured by Shimadzu Corporation can be cited. When measuring the visual reflectance, it is preferred to attach a black plate to the back of the substrate.

[0350] The visual reflectance Y value, total light transmittance and haze are the average values ​​measured at 10 locations.

[0351] The total light transmittance of the antiglare antireflection member in accordance with JIS K7361-1:1997 is preferably 50% or more, more preferably 80% or more, and even more preferably 90% or more.

[0352] The total light transmittance and the haze described below are measured with the light incident surface being the substrate side. The total light transmittance and the haze described below can be measured, for example, using a haze meter (model: HM-150) manufactured by Murakami Color Research Laboratory.

[0353] Regarding the antiglare antireflection member, when transparency is required, the haze according to JIS K7136:2000 is preferably 0.3% to 10%, more preferably 0.4% to 7%, more preferably 0.5% to 5%, more preferably 0.6% to 2.2%.

[0354] In addition, for applications requiring higher anti-glare properties, the haze of the anti-glare anti-reflection member is preferably 1% to 90%, more preferably 10% to 85%, and even more preferably 20% to 80%.

[0355] The arithmetic mean roughness Ra of the surface on the low refractive index layer side of the antiglare antireflection member is preferably 0.01 μm to 0.18 μm, more preferably 0.02 μm to 0.08 μm, and further preferably 0.03 μm to 0.07 μm.

[0356] The surface roughness of the low refractive index layer side is an average value obtained by measuring 10 locations.

[0357] Preferred ranges of Ra of the surface on the low refractive index layer side include 0.01 μm to 0.18 μm, 0.01 μm to 0.08 μm, 0.01 μm to 0.07 μm, 0.02 μm to 0.18 μm, 0.02 μm to 0.08 μm, 0.02 μm to 0.07 μm, 0.03 μm to 0.18 μm, 0.03 μm to 0.08 μm, and 0.03 μm to 0.07 μm.

[0358] In this specification, when measuring various physical properties such as film thickness, optical properties, and surface roughness, unless otherwise specified, the values ​​are measured under the conditions of a temperature of 23±5°C and a relative humidity of 40% to 65%. In addition, before starting each measurement and evaluation, the target sample is exposed to the above atmosphere for more than 30 minutes before measurement and evaluation.

[0359] <Size, shape, etc.>

[0360] The anti-glare anti-reflection component can be a single sheet cut into a specified size, or a roll-shaped form in which a long strip is wound into a roll. The size of the single sheet is not particularly limited, and the maximum diameter is about 2 inches or more and 500 inches or less. "Maximum diameter" refers to the maximum length when any two points of the anti-glare anti-reflection component are connected. For example, when the anti-glare anti-reflection component is a rectangle, the diagonal of the rectangle is the maximum diameter. In addition, when the anti-glare anti-reflection component is a circle, the diameter of the circle is the maximum diameter.

[0361] The width and length of the roll are not particularly limited. Generally speaking, the width is 500 mm or more and 8000 mm or less, and the length is 100 m or more and 10000 m or less. The anti-glare anti-reflection component in a roll form can be cut into a single piece for use according to the size of an image display device, etc. When cutting, it is preferred to remove the roll end with unstable physical properties.

[0362] In addition, the shape of a single sheet is not particularly limited, and it can be, for example, a polygon such as a triangle, a quadrilateral, a pentagon, or a circle, or a random amorphous shape. More specifically, when the anti-glare anti-reflection component is a quadrilateral, the aspect ratio is not particularly limited as long as there is no problem as a display screen. For example, horizontal:vertical = 1:1, 4:3, 16:10, 16:9, 2:1, 5:4, 11:8, etc. can be listed.

[0363] [Screening method for anti-glare and anti-reflection components]

[0364] The screening method of the antiglare antireflection member disclosed in the present invention comprises the following steps (1) and (2).

[0365] (1) A step of measuring a film thickness difference Δd of the low refractive index layer in an arbitrary 2 mm×2 mm region of an antiglare antireflection member having an antiglare layer and a low refractive index layer on a substrate, and calculating an average of Δd.

[0366] (2) A step of selecting a member satisfying the judgment condition that the average Δd is 7.0 nm or more and 40.0 nm or less as an antiglare antireflection member.

[0367] The method for screening anti-glare anti-reflection members preferably further includes one or more embodiments selected from the above-mentioned preferred embodiments of the anti-glare anti-reflection member of the present disclosure as additional determination conditions.

[0368] As an additional determination condition, for example, a determination condition that the haze according to JIS K7136:2000 is 0.3% or more and 10% or less can be cited.

[0369] According to the screening method of the anti-glare anti-reflection member of the present disclosure, it is possible to stably screen out an anti-glare anti-reflection member capable of suppressing coloration when observed from an oblique direction and suppressing local observation of bright spots.

[0370] [Polarizing plate]

[0371] The polarizing plate disclosed in the present invention is a polarizing plate having a polarizer, a first transparent protective plate arranged on one side of the polarizer, and a second transparent protective plate arranged on the other side of the polarizer, at least one of the first transparent protective plate and the second transparent protective plate is the above-mentioned anti-glare and anti-reflection component disclosed in the present invention, and the anti-glare and anti-reflection component is arranged in a manner that the surface of the low refractive index layer side faces the side opposite to the polarizer.

[0372] <Polarizer>

[0373] As polarizers, for example, there can be listed: sheet-type polarizers such as polyvinyl alcohol film, polyvinyl formal film, polyvinyl acetal film, ethylene-vinyl acetate copolymer saponified film, etc., which are dyed and stretched using iodine or the like; wire grid polarizers composed of a plurality of metal wires arranged in parallel; coating polarizers coated with lyotropic liquid crystal or dichroic guest-host material; and multilayer film polarizers, etc. It should be noted that these polarizers may be reflective polarizers having the function of reflecting polarized light components that are not transmitted.

[0374] <Transparent protective plate>

[0375] A first transparent protective plate is disposed on one side of the polarizer, and a second transparent protective plate is disposed on the other side. At least one of the first transparent protective plate and the second transparent protective plate is the above-mentioned anti-glare anti-reflection member of the present disclosure.

[0376] As the first transparent protective plate and the second transparent protective plate other than the anti-glare anti-reflection component, plastic films and glass can be listed. As plastic films, polyester films, polycarbonate films, cycloolefin polymer films and acrylic films can be listed. In order to make the mechanical strength good, their stretched films are preferred. Regarding glass, alkali glass, nitride glass, soda lime glass, borosilicate glass and lead glass can be listed. In addition, the glass of the transparent protective plate for protecting the polarizer is preferably used as other components of the image display device. For example, it is preferably used as a glass substrate of a liquid crystal display element and a transparent protective plate for protecting the polarizer.

[0377] It should be noted that the polarizer and the transparent protective plate are preferably bonded together by an adhesive. The adhesive can be a general adhesive, preferably a PVA-based adhesive.

[0378] The polarizing plate of the present disclosure may be a first transparent protective plate and a second transparent protective plate, both of which are the anti-glare film of the present disclosure, but preferably, one of the first transparent protective plate and the second transparent protective plate is the anti-glare film of the present disclosure. In addition, in the case where the polarizing plate of the present disclosure is used as a polarizing plate disposed on the light emitting surface side of the display element, the transparent protective plate on the light emitting surface side of the polarizer is preferably the anti-glare film of the present disclosure. On the other hand, in the case where the polarizing plate of the present disclosure is used as a polarizing plate disposed on the opposite side of the display element to the light emitting surface, the transparent protective plate on the opposite side of the polarizer to the light emitting surface is preferably the anti-glare film of the present disclosure.

[0379] [Surface panel for image display device]

[0380] The surface plate used in the image display device disclosed in the present invention is formed by bonding an anti-glare anti-reflection component to a resin plate or a glass plate, and the anti-glare anti-reflection component is the anti-glare anti-reflection component of the present invention mentioned above, and the anti-glare anti-reflection component is arranged in a manner such that the surface on the low refractive index layer side faces the side opposite to the resin plate or the glass plate.

[0381] The surface plate for the image display device is preferably configured in a manner that the surface of the side to which the anti-glare anti-reflection component is attached faces the surface side. In other words, the surface plate for the image display device is preferably configured in a manner that the surface of the side to which the anti-glare anti-reflection component is attached faces the side opposite to the display element.

[0382] As the resin plate or the glass plate, a resin plate or a glass plate generally used as a surface plate of an image display device can be used.

[0383] In order to improve the strength, the thickness of the resin plate or glass plate is preferably 10 μm or more. The upper limit of the thickness of the resin plate or glass plate is usually 5000 μm or less, but in recent years, the thinning of image display devices has been popular, so the upper limit is preferably 1000 μm or less, more preferably 500 μm or less, and further preferably 100 μm or less. The glass plate includes so-called "ultra-thin glass". Ultra-thin glass is sold by, for example, Samsung and Nippon Electric Glass.

[0384] [Image display device]

[0385] The image display device of the present disclosure is configured such that the antiglare antireflection member of the present disclosure is disposed on the display element with the low refractive index layer facing the opposite side of the display element, and the antiglare antireflection member is disposed on the surface.

[0386] As display elements, there can be listed EL display elements such as liquid crystal display elements, organic EL display elements, inorganic EL display elements, plasma display elements, etc., and further LED display elements such as micro LED display elements and mini LEDs can be listed. These display elements can also have a touch panel function inside the display element.

[0387] As the display mode of the liquid crystal of the liquid crystal display element, IPS mode, VA mode, multi-domain mode, OCB mode, STN mode, TSTN mode, etc. can be listed. In the case where the display element is a liquid crystal display element, a backlight source is required. The backlight source is configured on the side of the liquid crystal display element opposite to the side with the anti-glare film. As the backlight source, a backlight source using quantum dots and a backlight source using white light emitting diodes can be listed.

[0388] The image display device may be a foldable image display device or a rollable image display device. The image display device may have a curved surface. In addition, the image display device may be an image display device with a touch panel.

[0389] Example

[0390] Hereinafter, the present disclosure will be specifically described with reference to Examples and Comparative Examples. It should be noted that the present disclosure is not limited to the embodiments described in the Examples.

[0391] 1. Evaluation and measurement

[0392] The following measurements and evaluations were performed on the anti-glare anti-reflection components obtained in the examples and comparative examples. The results are shown in Table 2. In addition, unless otherwise specified, the atmosphere during each measurement and evaluation was: temperature 23±5°C, relative humidity 40% to 65%, and before each measurement and evaluation, the target sample was exposed to the aforementioned atmosphere for more than 30 minutes before the measurement and evaluation.

[0393] 1-1. Average of Δd

[0394] Ten samples A1 were prepared by cutting the anti-glare anti-reflection component into strips of 2 mm × 10 mm. Next, according to the description of steps z2 to z10 in the main text of the specification, the Δd representing the difference in film thickness of the low refractive index layer in the area of ​​2 mm × 2 mm was calculated for each of the ten samples A1, and their average value was taken as the average of Δd. The results are shown in Table 2. In addition, the average film thickness of the peak points and the average film thickness of the bottom of the ten samples A1 are shown in Table 2. In Table 2, "peak" represents the average film thickness of the peak points, and "bottom" represents the average film thickness of the bottom.

[0395] In the measurement of the surface shape in step z2, a white interference microscope (New View 6300, manufactured by Zygo Corporation) was used to perform measurement and analysis under the following conditions.

[0396] The Microscope Application of MetroPro ver8.1.5 was used for measurement, and the Microscope Application and Advanced Texture Application of MetroPro ver8.1.5 were used for analysis.

[0397] <Measurement conditions>

[0398] Objective lens: ×2.5

[0399] Image Zoom: ×2

[0400] [Measurement Controls]

[0401] Acquisition Mode: Scan

[0402] Camera Mode: 992×992 50Hz

[0403] Subtract Sys Err:Off

[0404] AGC: On

[0405] Phase Res: High

[0406] Connection Order:Location

[0407] Discon Action: Filter

[0408] Min Mod(%):0.001

[0409] Min Area Size: 7

[0410] Remove Fringes: On

[0411] Number of Averages: 0

[0412] FDA Noise Threshold: 10

[0413] Scan Length: 15um bipolar

[0414] Extended Scan Length: 1000μm

[0415] FDA Res:High

[0416] Camera resolution (interval per point): 2.215 μm

[0417] Measuring area: 2175.3μm×2175.3μm

[0418] [Surface Map Controls]

[0419] Removed: None

[0420] Sphere Radius: 0nm

[0421] Trim: 0

[0422] Trim Mode: All

[0423] Data Fill: On

[0424] Data Fill Max: 500

[0425] Filter:Off

[0426] FilterType: Gauss Spline

[0427] Filter Low Wavelength: 1100μm

[0428] Filter High Wavelen:200μm

[0429] Filter Low Freq:0.90909 1 / mm

[0430] Filter High Freq:5.00000 1 / mm

[0431] In the cutting of the embedded sample in step z7, a product named "Ultra Microtome EM UC7" manufactured by Leica Micro Systems was used. It should be noted that as a cutter, a product named "ULTRA 45°" manufactured by DiATOME was used, and as a grid, a collodion-coated grid ("Product No.: 150 mesh Cu") manufactured by Nissin EM was used.

[0432] In step z8, a scanning transmission electron microscope (STEM) with a product number of "SU-8000" manufactured by Hitachi High-Technologies Corporation was used, and the observation conditions of the STEM were as follows.

[0433] <Observation conditions of STEM>

[0434] Detector: TE

[0435] Accelerating voltage: 30 kV

[0436] Transmitter: 10μA

[0437] Probe current: Normal

[0438] Condenser lens 1:5.0

[0439] 1-2. Visual reflectivity Y value (reflectivity)

[0440] The samples were prepared by bonding a black plate (manufactured by KURARAY, trade name: COMOGLASS DFA2CG 502K (black), thickness: 2 mm) to the substrate side of the antiglare antireflection member of the Example and the Comparative Example via a 25 μm thick transparent adhesive layer (manufactured by PANAC, trade name: PANACLEAN PD-S1). The size of the sample was 5 cm×5 cm.

[0441] When the direction perpendicular to the low refractive index layer surface of the antiglare antireflection member is set to 0 degrees, light is incident on the sample from a direction of 5 degrees, and the visual reflectance Y value as the reflectance of the sample is measured based on the regular reflection light of the incident light.

[0442] Regarding the reflectivity, a spectroscopic reflectivity meter (manufactured by JASCO Corporation, trade name: V-7100) was used to measure the reflectivity under the conditions of a viewing angle of 2 degrees, a C light source, and a wavelength range of 380 nm to 780 nm. Then, the value representing the visual reflectivity calculated by the software (JASCO Spectrum Manager Ver2.0) for converting the result into the brightness felt by the human eye was used as the visual reflectivity Y value, and the reflectivity was calculated. 10 locations were measured in the sample, and the average value of the 10 locations was used as the reflectivity of each embodiment and comparative example. A mask of 5 mm × 10 mm was used for the measurement. Therefore, the size of the reflectivity measurement spot when the incident angle is 5 degrees is 50.2 mm 2 The case where the reflectance was 1.5% or less was designated as "A", and the case where the reflectance exceeded 1.5% and was 2.0% or less was designated as "B".

[0443] 1-3. Coloring in the oblique direction

[0444] For the sample made in 1-2, use the same spectral reflectance measuring instrument as 1-2, make light incident on the sample from a direction of 60 degrees, and measure the wavelength spectral reflectance of the sample when the wavelength range is above 380nm and below 780nm based on the regular reflected light of the incident light. The measurement conditions are: the viewing angle is 2 degrees and the light source is C. A mask of 5mm×10mm is used for measurement. Therefore, the size of the reflectance measurement spot when the incident angle is 60 degrees is 100.0mm 2 .

[0445] When the lowest value of the spectral reflectance in the above-mentioned wavelength range is defined as the bottom reflectance, the "reflectance / bottom reflectance of the central wavelength (700nm) of red", "reflectance / bottom reflectance of the central wavelength (550nm) of green", and "reflectance / bottom reflectance of the central wavelength (450nm) of blue" are calculated respectively, and then their total value is calculated.

[0446] It can be said that the closer the total value is to 3, the more the coloring in the oblique direction can be suppressed. The total value of 3.530 or less is a passing level, the value exceeding 3.530 is "C", the value exceeding 3.500 and below 3.530 is "B", and the value below 3.500 is "A".

[0447] 1-4. Highlights

[0448] The sample prepared in 1-2 was placed on a horizontal table with the low refractive index layer side facing upward, and the presence of bright spots was visually evaluated from various angles where the reflected light of the fluorescent lamp used as lighting was observed in a bright room environment. The conditions of the bright room environment are: the illumination on the low refractive index layer of the sample is greater than 500 lux and less than 1000 lux. For lighting, a straight tube three-wavelength neutral white fluorescent lamp of the Hf32 type was used. The lighting position was 2m above the horizontal platform in the vertical direction. The evaluation was performed from above at a straight-line distance of about 50cm from the sample. Furthermore, in the bright room environment, the presence of bright spots was visually evaluated from various angles while the sample was held in the hand and the distance between the sample and the face was set to be greater than 20cm and less than 30cm.

[0449] 3 points were given to those who did not care about the bright spot, 2 points were given to those who could not explain it, and 1 point was given to those who cared about the bright spot. Five people in each age group from their 20s to their 50s, a total of 20 subjects, evaluated. The average score of the 20 people's evaluation was calculated and ranked according to the following criteria.

[0450] <Evaluation Criteria>

[0451] A: Average score is 2.5 or above

[0452] B: Average score is 2.0 or more and less than 2.5

[0453] C: Average score less than 2.0

[0454] 1-5. Anti-glare (AG)

[0455] The sample made in 1-2 is arranged on a horizontal table with the low refractive index layer side facing upward. In a bright room environment, 5 subjects of each age group from 20 to 50 years old, a total of 20 subjects, are visually inspected from above at a straight-line distance of about 50 cm from the sample, and evaluate whether the anti-glare property is obtained to the extent that there is no worry about the reflection of the subject himself. The conditions of the bright room environment are: the illumination on the low refractive index layer of the sample is more than 500 lux and less than 1000 lux. A straight tube three-wavelength neutral white fluorescent lamp of the Hf32 type is used for lighting. The position of the lighting is a height of 2m above the vertical direction from the horizontal platform. Furthermore, a sample with the same structure as the sample made in 1-2 and increased in size to A4 size is made. Using the above-mentioned A4-sized sample, the anti-glare property is evaluated in the same manner as above. Anti-glare property is evaluated according to the following benchmarks.

[0456] <Evaluation Criteria>

[0457] A: There are more than 14 people who answered well

[0458] B: The number of people who answered well is 7 or more and 13 or less

[0459] C: There are less than 6 people who answered well

[0460] 1-6. Total transmittance (Tt) and haze (Hz)

[0461] The total light transmittance specified in JIS K7361-1: 1997 and the haze specified in JIS K7136: 2000 of the antiglare antireflection members of Examples and Comparative Examples were measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory). The light incident surface was the substrate side.

[0462] Regarding the total light transmittance, 90% or more was designated as "A", and less than 90% was designated as "B".

[0463] Regarding the haze, 2.2% or less was designated as "A", more than 2.2% and 5.0% or less was designated as "B", and more than 5.0% was designated as "C".

[0464] 1-7. Tensile elastic modulus and water vapor transmission rate of substrate

[0465] The tensile modulus and water vapor permeability of the substrate were measured according to the description in the main text of the specification. For the tensile modulus, the substrate with a modulus of 3.5 GPa or more was designated as "A", and the substrate with a modulus of 2.5 GPa or more and less than 3.5 GPa was designated as "B". For the water vapor permeability, 100 g / m 2 Base materials with a thickness of less than 100 g / m2 are designated as “A”. 2 The substrate for each day is designated as "B".

[0466] 2. Synthesis of Compound A (Urethane Acrylate Oligomer)

[0467] After introducing air into a reaction vessel equipped with a stirrer, a thermometer, a cooling tube, and a nitrogen inlet tube, 10.0 parts by mass of 1,3-butanediol, 10.0 parts by mass of 1,4-butanediol, 0.1 parts by mass of p-methoxyphenol, 0.1 parts by mass of dibutyltin dilaurate, and 100.0 parts by mass of methyl ethyl ketone were added, and the temperature was raised to 50°C while stirring under a nitrogen stream. On the other hand, 50.3 parts by mass of isophorone diisocyanate was added to a dropping container, and it was uniformly dropped into the reaction vessel over 1 hour. At this time, the temperature of the reaction vessel was maintained at 50±3°C. After keeping the temperature for 1 hour while stirring, 0.1 parts by mass of p-methoxyphenol and 0.1 parts by mass of dibutyltin dilaurate were further added, and the temperature was raised to 60°C while stirring under a nitrogen stream. Thereafter, 176.0 parts by mass of a mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate at a mass ratio of 80 / 20, which had been placed in the dropping container, was uniformly dropped into the reaction container over 1 hour while stirring.

[0468] After the addition is completed, the dropping container is cleaned with 120.0 parts by mass of methyl ethyl ketone, and the cleaned solution is directly put into the reaction container. After further stirring and keeping warm for 2 hours, the temperature is raised to 75°C. Then, stirring and keeping warm are continued at 75±3°C until the peak derived from isocyanate in the infrared absorption spectrum disappears. In about 4 to 6 hours, the peak derived from isocyanate disappears. After confirming that the peak disappears, the temperature is lowered to 60°C, 7.0 parts by mass of methanol are added, and the temperature is kept at 60±3°C for 30 minutes. Then 120.8 parts by mass of methyl ethyl ketone are added to obtain a transparent resin solution. Finally, the solvent is removed using an evaporator to obtain a urethane acrylate oligomer as compound A. The weight average molecular weight of the obtained compound A is 2000.

[0469] 3. Preparation of coating solution

[0470] (1) Anti-glare layer coating liquid 1

[0471] 5 parts by mass of a photopolymerization initiator (manufactured by IGM Resins BV, trade name "ESACUR1"), 1 part by mass of particles 1 (acrylic beads, average particle size of 2.0 μm, coefficient of variation of 10.4%, refractive index of 1.535), and 1 part by mass of a leveling agent (manufactured by DIC, trade name "F-568", solid content of 5% by mass) were mixed with 100 parts by mass of the resin solid content of compound A. The mixture was diluted with a mixed solvent of methyl ethyl ketone and cyclopentanone in a mass ratio of 70 / 30 so that the solid content concentration became 50% by mass, thereby preparing an anti-glare layer coating solution 1.

[0472] (2) Anti-glare layer coating liquid 2

[0473] An antiglare layer coating liquid 2 was prepared in the same manner as in (1) except that the content of the particles 1 was changed to 3 parts by mass based on 100 parts by mass of the resin solid content of the compound A.

[0474] (3) Anti-glare layer coating liquid 3

[0475] An anti-glare layer coating liquid 3 was prepared in the same manner as (1), except that particle 1 was replaced with particle 2 (acrylic beads, average particle size of 3.0 μm, coefficient of variation of 9.8%, refractive index of 1.535) and the content of particle 2 was changed to 3 parts by mass relative to 100 parts by mass of the resin solid component of compound A.

[0476] (4) Anti-glare layer coating liquid 4

[0477] An anti-glare layer coating liquid 4 was prepared in the same manner as (1), except that particle 1 was replaced with particle 2 (acrylic beads, average particle size of 3.0 μm, coefficient of variation of 9.8%, refractive index of 1.535) and the content of particle 2 was changed to 5 parts by mass relative to 100 parts by mass of the resin solid content of compound A.

[0478] (5) Anti-glare layer coating liquid 5

[0479] Anti-glare layer coating liquid 5 was prepared in the same manner as (1), except that particle 1 was changed to particle 3 (acrylic beads, average particle size of 3.5 μm, coefficient of variation of 10.7%, refractive index of 1.535) and the content of particle 3 was changed to 5 parts by mass relative to 100 parts by mass of the resin solid component of compound A.

[0480] (6) Anti-glare layer coating liquid 6

[0481] An anti-glare layer coating liquid 6 was prepared in the same manner as (1), except that particle 1 was replaced with particle 2 (acrylic beads, average particle size of 3.0 μm, coefficient of variation of 9.8%, refractive index of 1.535) and the content of particle 2 was changed to 4 parts by mass relative to 100 parts by mass of the resin solid component of compound A.

[0482] (7) Anti-glare layer coating liquid 7

[0483] Anti-glare layer coating liquid 7 was prepared in the same manner as (1), except that particle 1 was replaced with particle 2 (acrylic beads, average particle size of 3.0 μm, coefficient of variation of 9.8%, refractive index of 1.535) and the content of particle 2 was changed to 2 parts by mass relative to 100 parts by mass of the resin solid content of compound A.

[0484] (8) Low refractive index layer coating liquid 1

[0485] With respect to 1 part by mass of the resin solid content of the compound (A), 0.1 parts by mass of a photopolymerization initiator (manufactured by IGM Resins BV, trade name "Omnirad127"), 1.6 parts by mass of hollow silica particles (average particle size of 60 nm, refractive index of 1.212), 0.7 parts by mass of solid silica particles (average particle size of 15 nm), and 0.01 parts by mass of a leveling agent (manufactured by Shin-Etsu Silicone, trade name "X-22-164E") were mixed. The mixture was diluted with a mixed solvent of methyl isobutyl ketone and propylene glycol monomethyl ether acetate in a mass ratio of 70 / 30 so that the solid content concentration became 5% by mass, thereby preparing a coating liquid 1 for a low refractive index layer.

[0486] (9) Low refractive index layer coating liquid 2

[0487] A low refractive index layer coating liquid 2 was prepared in the same manner as in (8) except that the mixed solvent was changed to a mixed solvent of methyl isobutyl ketone and propylene glycol monomethyl ether propionate in a mass ratio of 70 / 30.

[0488] (10) Low refractive index layer coating liquid 3

[0489] A low refractive index layer coating liquid 3 was prepared in the same manner as in (8) except that the mixed solvent was changed to a mixed solvent of methyl ethyl ketone and propylene glycol monomethyl ether acetate in a mass ratio of 70 / 30.

[0490] (11) Low refractive index layer coating liquid 4

[0491] With respect to 1 part by mass of pentaerythritol triacrylate, 0.1 parts by mass of a photopolymerization initiator (manufactured by IGM Resins BV, trade name "Omnirad 127"), 1.6 parts by mass of hollow silica particles (average particle size of 60 nm, refractive index of 1.212), 0.7 parts by mass of solid silica particles (average particle size of 15 nm), and 0.01 parts by mass of a leveling agent (manufactured by Shin-Etsu Silicone, trade name "X-22-164E") were mixed. The mixture was diluted with a mixed solvent of methyl isobutyl ketone and propylene glycol monomethyl ether acetate in a mass ratio of 70 / 30 so as to give a solid content concentration of 5% by mass, thereby preparing a coating liquid 4 for a low refractive index layer. (The coating liquid 4 for a low refractive index layer is equivalent to a coating liquid obtained by replacing compound A of the coating liquid 1 for a low refractive index layer with pentaerythritol triacrylate.)

[0492] 4. Preparation and production of polyester film

[0493] [Polyester film 1 (substrate used in Example 7)]

[0494] 1 kg of PET (melting point: 258°C, absorption center wavelength: 320 nm) and 0.1 kg of ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinone-4-one)) were melt-mixed at 280°C in a kneader to prepare pellets containing the ultraviolet absorber. The pellets and PET with a melting point of 258°C were put into a single screw extruder, melt-mixed at 280°C, extruded from a T-die, and cast on a casting drum whose surface temperature was controlled to 25°C to obtain a cast film. The amount of the ultraviolet absorber in the cast film was 1 part by mass relative to 100 parts by mass of PET.

[0495] The obtained cast film was heated by a roller set at 95°C, and then the film temperature at a point of 180 mm in the 480 mm stretching interval was 103°C while being heated from both sides of the film by a radiation heater, and the film was stretched 3.6 times in the flow direction, and then temporarily cooled. In Example 1, the time for the cast film to pass through the stretching interval in the flow direction was 0.192 seconds. The starting point of the stretching interval was the stretching roller A, and the end point was the stretching roller B, and the stretching rollers A and B each had two press rollers.

[0496] Next, both surfaces of the uniaxially stretched film were subjected to corona discharge treatment in air so that the wetting tension of the base film was 55 mN / m, and a "lubricating layer coating liquid containing a polyester resin having a glass transition temperature of 18°C, a polyester resin having a glass transition temperature of 82°C, and silica particles having an average particle size of 100 nm" was applied to the corona discharge treated surfaces of both surfaces of the film to form a lubricating layer.

[0497] Next, the uniaxially stretched film was introduced into a tenter, and after being preheated with hot air at 95°C, it was stretched 4.9 times in the width direction of the film at a temperature of 105°C in the first stage and 140°C in the second stage. Here, when the transverse stretching interval is divided into two parts, the stretching is performed in two stages in such a way that the stretching amount of the film at the middle point of the transverse stretching interval becomes 80% of the stretching amount at the end of the transverse stretching interval. The aforementioned "stretching amount" refers to the difference between the film width at the measuring point and the film width before stretching. For the transversely stretched film, the film is heat-treated in stages directly in the tenter using hot air at a heat treatment temperature of 180°C to 245°C, and then a 1% relaxation treatment is performed in the width direction under the same temperature conditions, and then it is rapidly cooled to 100°C, and then a 1% relaxation treatment is performed in the width direction, and then it is rolled up to obtain a polyester film 1 with a thickness of 40μm.

[0498] According to the description in the specification, the E 0-20 . Polyester film 1 E 0-20 It is 2.05μm / g.

[0499] [Polyester film 2 (substrate used in Example 8)]

[0500] A polyester film 2 having a thickness of 40 μm was obtained in the same manner as the polyester film 1 except that the stretching section in the flow direction was changed from 480 mm to 460 mm and the stretching ratio in the width direction was changed from 4.9 to 5.1. For the polyester film 2, the time for the cast film to pass through the stretching section in the flow direction was 0.184 seconds.

[0501] According to the description in the specification, the E of the polyester film 2 was measured. 0-20 . Polyester film 2 E 0-20 It is 1.89μm / g.

[0502] [Polyester film 3 (substrate used in Example 9)]

[0503] A polyester film 3 having a thickness of 40 μm was obtained in the same manner as the polyester film 1 except that the stretching section in the flow direction was changed from 480 mm to 450 mm and the stretching ratio in the width direction was changed from 4.9 to 5.3. The time for the cast film 3 to pass through the stretching section in the flow direction was 0.180 seconds.

[0504] According to the description in the specification, the E 0-20 . Polyester film 3 E 0-20 It is 1.67μm / g.

[0505] [Polyester film 4 (substrate used in Example 12)]

[0506] As the polyester film 4, a commercially available biaxially stretched polyester film (Toyobo Co., Ltd., trade name: "Cosmoshine A4360", thickness: 50 μm) was prepared.

[0507] According to the description in the specification, the E of the polyester film 4 was measured. 0-20 . Polyester film 4 E 0-20 It is 0.97μm / g.

[0508] 5. Production of anti-glare and anti-reflective components

[0509] [Example 1]

[0510] The anti-glare layer coating liquid 1 was applied at a wet weight of 10 g / m 2 The substrate (triacetyl cellulose film with a thickness of 80 μm, in-plane phase difference: 2 nm, tensile elastic modulus: 4.3 GPa, water vapor transmission rate: 487 g / m 2 / day), dried at 80°C for 30 seconds, and then irradiated with 100 mJ / cm 2 The anti-glare layer is formed by the ultraviolet rays of the substrate to have a dry film thickness of 5 μm. The direction of the drying wind is substantially horizontal to the conveying direction of the substrate and opposite to the conveying direction of the substrate. In addition, the wind speed of the drying wind is 30 m / s. The conveying speed of the substrate is 20 m / min.

[0511] Then, the wet mass becomes 2g / m 2 The low refractive index layer coating solution 1 was applied on the anti-glare layer in a manner, dried at 60° C. for 30 seconds, and then irradiated with 200 mJ / cm 2 The ultraviolet rays of the substrate were used to form a low refractive index layer with an average film thickness of 100 nm, thereby obtaining the anti-glare anti-reflection component of Example 1. The direction of the drying wind was substantially horizontal to the conveying direction of the substrate and opposite to the conveying direction of the substrate. In addition, the wind speed of the drying wind was set to 25 m / s.

[0512] The substrate was heated from the formation of the antiglare layer to the application of the low refractive index layer coating solution, and the substrate temperature was set to 40° C. when the low refractive index layer coating solution 1 was applied on the antiglare layer.

[0513] [Examples 2 to 6]

[0514] Antiglare antireflection members of Examples 2 to 6 were obtained in the same manner as in Example 1 except that the following antiglare layer coating liquid was used as the antiglare layer coating liquid.

[0515] Anti-glare layer coating liquid of Example 2: Anti-glare layer coating liquid 2

[0516] Anti-glare layer coating liquid of Example 3: Anti-glare layer coating liquid 3

[0517] Anti-glare layer coating liquid of Example 4: Anti-glare layer coating liquid 4

[0518] Anti-glare layer coating liquid of Example 5: Anti-glare layer coating liquid 6

[0519] Anti-glare layer coating liquid of Example 6: Anti-glare layer coating liquid 7

[0520] [Examples 7 to 12]

[0521] Antiglare antireflection members of Examples 7 to 12 were obtained in the same manner as in Example 3 except that the substrate was changed to the following substrate.

[0522] Substrate of Example 7: Polyester film 1 (in-plane phase difference: 502 nm, tensile elastic modulus: 4.8 GPa, water vapor transmission rate: 58 g / m 2 / day、Thickness:40μm、E 0-20 : 2.05μm / g, pencil hardness: F (5 times / 5 times)

[0523] Substrate of Example 8: Polyester film 2 (in-plane phase difference: 982 nm, tensile elastic modulus: 4.8 GPa, water vapor transmission rate: 55 g / m 2 / day、Thickness:40μm、E 0-20 : 1.89μm / g, pencil hardness: F (5 times / 5 times)

[0524] Substrate of Example 9: Polyester film 3 (in-plane phase difference: 1597 nm, tensile elastic modulus: 4.9 GPa, water vapor transmission rate: 57 g / m 2 / day、Thickness:40μm、E 0-20 : 1.67μm / g, pencil hardness: F (4th / 5th)

[0525] Substrate of Example 10: 40 μm thick acrylic film (in-plane phase difference: 3 nm, tensile elastic modulus: 2.6 GPa, water vapor transmission rate: 85 g / m 2 / day, thickness: 40μm)

[0526] Substrate of Example 11: 47 μm thick cycloolefin film (in-plane phase difference: 99 nm, tensile elastic modulus: 3.0 GPa, water vapor transmission rate: 38 g / m 2 / day, thickness: 47μm)

[0527] Substrate of Example 12: Polyester film 4 (in-plane phase difference: 1899 nm, tensile elastic modulus: 4.8 GPa, water vapor transmission rate: 55 g / m 2 / day、Thickness:50μm、E0-20 : 0.97μm / g, pencil hardness: 3B (5 times / 5 times)

[0528] <Pencil hardness>

[0529] The polyester films 1 to 4 as the substrates of Examples 7 to 9 and 12 were heated at 100° C. for 10 minutes. The heated polyester films were subjected to a pencil hardness test.

[0530] For the pencil hardness test, the pencil hardness test specified in JIS K5600-5-4:1999 is used as a reference, and the load, speed and judgment conditions are changed from the provisions of JIS. Specifically, the load is set to 100g and the speed is set to 3mm / s. After applying a load to the polyester film as a sample, the test piece is heated again at 100°C for 10 minutes before visually evaluating the damage. Then, visually evaluate the damage of the heated sample. The qualified judgment condition is: in 5 evaluations, there are more than 3 times without damage. For example, the following judgment method is adopted: If the hardness 2B does not cause damage in more than 3 out of 5 times, the hardness 2B is qualified, and then enters the test at a harder hardness.

[0531] In the description of the substrates of Examples 7 to 9 and 12, the pencil hardness of each sample is shown, and the number of evaluations in which no scratches were caused among 5 evaluations is shown.

[0532] Regarding the pencil hardness F, the case where no scratches occurred in three or more of five evaluations was considered to be a pass level.

[0533] [Comparative Example 1]

[0534] An antiglare antireflection member of Comparative Example 1 was obtained in the same manner as in Example 1 except that the antiglare layer coating liquid 1 was changed to the antiglare layer coating liquid 5.

[0535] [Comparative Example 2]

[0536] An antiglare antireflection member of Comparative Example 2 was obtained in the same manner as in Example 1 except that the antiglare layer coating liquid 1 was changed to the antiglare layer coating liquid 4 and the low refractive index layer coating liquid 1 was changed to the low refractive index layer coating liquid 2.

[0537] [Comparative Example 3]

[0538] An antiglare antireflection member of Comparative Example 3 was obtained in the same manner as in Example 1 except that the low-refractive-index layer coating liquid 1 was changed to the low-refractive-index layer coating liquid 3.

[0539] [Comparative Example 4]

[0540] An antiglare antireflection member of Comparative Example 4 was obtained in the same manner as in Example 1 except that the antiglare layer coating liquid 1 was changed to the antiglare layer coating liquid 4 and the low refractive index layer coating liquid 1 was changed to the low refractive index layer coating liquid 4.

[0541] [Comparative Example 5]

[0542] The anti-glare anti-reflection component of Comparative Example 5 was obtained in the same manner as in Example 1, except that heating was not performed from the substrate side during the period from the formation of the anti-glare layer to the application of the low-refractive index layer coating liquid, and the substrate temperature at the time of applying the low-refractive index layer coating liquid 1 on the anti-glare layer was changed to 20°C.

[0543] [Comparative Example 6]

[0544] The antiglare antireflection member of Comparative Example 6 was obtained in the same manner as in Example 3 except that the direction of the drying wind when drying the low refractive index layer coating liquid was changed to a direction perpendicular to the substrate and the wind speed was changed to 10 m / s.

[0545] Table 1 shows some of the materials and production conditions of Examples 1 to 12 and Comparative Examples 1 to 6.

[0546] [Table 1]

[0547] Table 1

[0548]

[0549] In Table 1, "PETA" represents pentaerythritol triacrylate, "MIBK" represents methyl isobutyl ketone, "PGM-A" represents propylene glycol monomethyl ether acetate, and "PGM-P" represents propylene glycol monomethyl ether propionic acid.

[0550] [Table 2]

[0551]

[0552] From Tables 1 and 2, it can be confirmed that the antiglare antireflection members of Examples having an average Δd of 7.0 nm or more and 40.0 nm or less can suppress coloration when observed from an oblique direction and can suppress local observation of bright spots.

[0553] The criteria for the comprehensive evaluation in Table 2 are as follows.

[0554] AA: All evaluations were A or higher.

[0555] A: There is one B rating, and all other ratings are A or above.

[0556] B: There are 2 B ratings and all other ratings are A or above.

[0557] C: There is one C evaluation or three or more B evaluations.

[0558] Description of symbols

[0559] 100: base material;

[0560] 200: Anti-glare layer;

[0561] 210: adhesive resin;

[0562] 220: Particles;

[0563] 300: low refractive index layer;

[0564] 1000: Anti-glare and anti-reflective components;

[0565] 2000: Sample A1;

[0566] 11: container;

[0567] 12: Receiver;

[0568] 21: Piping for test fluid;

[0569] 22: Compressed air piping;

[0570] 23: Return piping;

[0571] 31, 32: flow meter;

[0572] 41, 42: pressure gauge;

[0573] 50: injection part;

[0574] 51: nozzle;

[0575] 52: housing;

[0576] 60: cross-sectional profile obtaining unit;

[0577] 70: plastic film;

[0578] 81: Sample mounting table;

[0579] 82: support body;

[0580] 500: Erosion rate measuring device;

[0581] A1: water;

[0582] A2: spherical silica;

[0583] A3: Air;

[0584] A4: The plastic film is worn out.

Claims

1. An anti-glare anti-reflection component, comprising an anti-glare layer and a low refractive index layer on a substrate, wherein: The substrate is a plastic film, For the plastic film, the average of the erosion rates from the surface of the plastic film to a depth of 20 μm is defined as E. 0-20 When E 0-20 1.4μm / g or more, The low refractive index layer comprises a binder resin, hollow particles and non-hollow particles, When the difference in film thickness of the low refractive index layer in an arbitrary 2 mm×2 mm region of the antiglare antireflection member is defined as Δd, the average of Δd is 7.0 nm or more and 40.0 nm or less, The E 0-20 The measurement conditions are as follows: A test liquid is placed in a container: the test liquid is a mixture of pure water, a dispersion liquid, and spherical silica having an average particle size within ±8% based on 4.2 μm in a mass ratio of 968:2:30; the test liquid in the container is fed to a nozzle; compressed air is fed into the nozzle; the test liquid is accelerated in the nozzle; a predetermined amount of the test liquid is jetted vertically toward the plastic film from a jet hole at the end of the nozzle so that the spherical silica in the test liquid collides with the plastic film; the cross-sectional shape of the nozzle is a square of 1 mm×1 mm; the distance between the jet hole and the plastic film is 4 mm; and the flow rates of the test liquid and the compressed air supplied to the nozzle, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are predetermined values ​​adjusted by calibration described later. After a predetermined amount of the test liquid is sprayed, the spraying of the test liquid is temporarily stopped. After temporarily stopping the spraying of the test liquid, measuring the cross-sectional profile of the portion of the plastic film that collides with the spherical silica in the test liquid, The following operation is performed until the depth of the cross-sectional profile exceeds 20 μm: the operation includes three steps of a step of spraying a predetermined amount of the test liquid from the spray hole, a step of temporarily stopping the spraying of the test liquid after spraying the predetermined amount of the test liquid, and a step of measuring the cross-sectional profile after temporarily stopping the spraying of the test liquid as one cycle, and then, in each cycle until the depth of the cross-sectional profile reaches 20 μm, the erosion rate (μm / g) of the plastic film is calculated by dividing the depth (μm) of the cross-sectional profile advanced in each cycle by the spraying amount (g) of the test liquid in each cycle, and the erosion rate of the plastic film in each cycle until the depth of the cross-sectional profile reaches 20 μm is averaged to calculate the E 0-20 , The correction is as follows: The test liquid is stored in the container, the test liquid in the container is transported to the nozzle, compressed air is transported into the nozzle, the test liquid is accelerated in the nozzle, and an arbitrary amount of the test liquid is vertically sprayed from the spray hole at the end of the nozzle to the acrylic plate with a thickness of 2 mm, so that the spherical silica in the test liquid collides with the acrylic plate, the cross-sectional shape of the nozzle is a square of 1 mm×1 mm, and the distance between the spray hole and the acrylic plate is 4 mm, After spraying an arbitrary amount of the test liquid, the spraying of the test liquid is temporarily stopped, and after the spraying of the test liquid is temporarily stopped, the cross-sectional profile of the portion of the acrylic plate that collides with the spherical silica in the test liquid is measured, The corrosion rate (μm / g) of the acrylic plate is calculated by dividing the depth (μm) of the cross-sectional profile by an arbitrary amount (g). The erosion rate of the acrylic plate is set as a qualified condition within the range of ±5% based on 1.88 (μm / g). The flow rates of the test liquid and the compressed air, the pressure of the compressed air, and the pressure of the test liquid in the nozzle are adjusted to perform correction so that the erosion rate of the acrylic plate falls within the range.

2. The anti-glare anti-reflection member according to claim 1, wherein The anti-glare layer includes a binder resin and particles.

3. The anti-glare anti-reflection member according to claim 1, wherein The hollow particles are hollow silica particles, and the non-hollow particles are non-hollow silica particles.

4. The anti-glare anti-reflection component according to claim 1 or 2, wherein: The average thickness of the low refractive index layer is 80 nm or more and 120 nm or less.

5. The anti-glare anti-reflection member according to claim 1 or 2, wherein: The anti-glare layer is connected to the low refractive index layer.

6. The anti-glare anti-reflection member according to claim 1 or 2, wherein: The visual reflectance Y value measured from the side having the low refractive index layer at a light incident angle of 5 degrees is 3% or less.

7. The anti-glare anti-reflection member according to claim 1 or 2, wherein: The haze of JIS K7136:2000 is 0.3% or more and 10% or less.

8. A polarizing plate comprising: a polarizer; a first transparent protective plate disposed on one side of the polarizer; and a second transparent protective plate disposed on the other side of the polarizer, wherein: At least one of the first transparent protective plate and the second transparent protective plate is the anti-glare anti-reflection member according to any one of claims 1 to 7, The polarizing plate is configured such that the anti-glare anti-reflection member is disposed such that the surface on the low refractive index layer side faces the opposite side to the polarizer.

9. A surface plate for an image display device, which is formed by laminating an anti-glare anti-reflection component to a resin plate or a glass plate, wherein: The anti-glare anti-reflection member is the anti-glare anti-reflection member according to any one of claims 1 to 7, The surface plate for the image display device is formed by placing the antiglare antireflection member so that the surface on the low refractive index layer side faces the side opposite to the resin plate or the glass plate.

10. An image display device, wherein: The image display device is a device in which the anti-glare anti-reflection member according to any one of claims 1 to 7 is arranged on the display element with the surface on the low refractive index layer side facing the opposite side to the display element, and the anti-glare anti-reflection member is arranged on the surface.

11. A method for screening anti-glare and anti-reflection components, wherein: The screening method of the anti-glare anti-reflection component comprises the following steps (1) and (2): (1) measuring a film thickness difference Δd of the low refractive index layer in an arbitrary 2 mm×2 mm area of ​​an antiglare antireflection member having an antiglare layer and a low refractive index layer on a substrate, and calculating an average of Δd; (2) The average Δd is 7.0 nm or more and 40.0 nm or less as a determination condition, and members satisfying the determination condition are selected as antiglare antireflection members.

Citation Information

Patent Citations

  • Antireflection film

    JP2016218179A

  • Anti-glare Anti-reflection film and image display device including the same

    JP2018197829A

  • Anti-reflection film

    JP2020008877A

  • Antireflection film, process for producing antireflection film, polarizing plate, and display device

    WO2008084604A1